Silicon phenylene polymers
The silicon phenylene polymer prepared by Grignard reaction uses specific group composition and free radical polymerization to solve the problems of high dielectric loss and poor mechanical properties of silicon phenylene polymers in the prior art, and achieve low dielectric Loss and good mechanical properties of silicon phenylene polymers suitable for radio frequency applications.
Patent Information
- Application Number
- CN202280096095.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-17
- Publication Date
- 2025-01-03
- Estimated Expiration
- Not applicable · inactive patent
Smart Images

Figure BDA0005133672240000101 
Figure BDA0005133672240000111 
Figure BDA0005133672240000451
Abstract
Description
[0001] The present invention relates to free radical curable silphenylene polymers, methods for their preparation and their use as adhesives in radio frequency applications. Background Art
[0002] With the development of radio frequency technology for wireless communications, the demand for materials that enable this technology has increased. This involves all parts of materials such as copper foil, adhesives, glass fibers, etc. In the case of adhesives, the epoxy resins conventionally used for the production of copper-faced laminates and subsequently for the production of circuit boards can no longer be used because the dielectric loss factor of epoxy resins is too high. Polytetrafluoroethylene has a very low dielectric loss factor and is very useful for radio frequency applications on this basis, which has other disadvantages, especially poor processability and poor adhesion properties, and these make it desirable to have alternatives. Since polyphenylene ethers combine a low dielectric loss factor with good mechanical and thermal properties and water resistance, they are currently widely used as adhesives in this application field. In addition, other organic polymers are currently also considered in current development activities in this application field, examples being bismaleimide polymers, bismaleimide-triazine copolymers and hydrocarbon resins, and other examples can be supplemented in the list.
[0003] Polyorganosiloxane has substantially excellent heat resistance, weather resistance, and hydrophobicity, is flame retardant, and has a low dielectric loss factor.
[0004] These performance characteristics qualify not only the organic polymers mentioned, but also polyorganosiloxanes, for use as adhesives for the production of RF-compatible copper-faced laminates and components such as circuit boards and antennas. It is therefore clear that the positive properties of these classes of materials can be used for modern RF applications, and they can be used in each case alone or in combination with one another to achieve a symbiotic increase in their performance capabilities. Experiments in this direction have already been documented in the prior art.
[0005] Polar substituents are undesirable here because they increase the dielectric loss factor. In this article, polyorganosiloxanes have inherent disadvantages over other organic binders because their skeletons are usually composed of silicon atoms and oxygen atoms alternately. According to the electronegativity scale of Allred and Rochow, the difference in electronegativity between silicon and oxygen is 3.50-1.74=1.76. Here, the electronegativity of silicon is 1.74, and 3.5 is the electronegativity of oxygen. In contrast, the difference in electronegativity between carbon and oxygen is only 3.5-2.5=1.0, where 2.5 is the electronegativity of carbon. It is known that the difference in electronegativity can be shielded spatially and does not manifest itself externally, such as in the case of polytetrafluoroethylene, which exhibits excellent dielectric properties despite the electronegativity difference between carbon and fluorine of 1.67. For symmetrical polydiorganosiloxanes, such as polydimethylsiloxane, a similar shielding effect can be assumed. However, in contrast to polytetrafluoroethylene, polydimethylsiloxane does not have working properties suitable for use as an adhesive for radio frequency applications. For example, with polydiorganosiloxanes, the production of prepregs and their subsequent curing is not possible, and the viscosity obtained is not high enough to prevent the polydiorganosiloxanes from flowing away under the effect of the heat from the molten tin as part of the welding process. Even by crosslinking, such as the free radical polymerization of the adhesives used, which is preferred for the production of metal-faced laminates, it is not possible for polydiorganosiloxanes to obtain sufficient mechanical strength under thermal exposure. Unlike highly crosslinked elements, which are dimensionally stable even under temperature loads, the crosslinking of polydiorganosiloxanes under the influence of heat, as required by the present application, can produce reversibly deformable polymers, i.e. elastomers. In addition, polydiorganosiloxanes are incompatible with organic polymers, which significantly limits (if not actually excludes) the possibility of formulating suitable adhesive mixtures.
[0006] Candidate binders for radio frequency applications include polyorganosiloxanes, which have a three-dimensional backbone structure and which are chemically crosslinked to form thermosetting materials. Corresponding examples are known in the patent literature: see, for example, US2016 / 0244610 (compositions of mixtures of ethylenically unsaturated MQ resins and unsaturated modified polyphenylene ethers), US2018 / 0220530 (compositions of mixtures of polyphenylene ethers and MT, MDT, MDQ and MTQ silicone resins) or US2018 / 0215971 (compositions of mixtures of polyphenylene ethers and TT and TQ silicone resins).
[0007] The target dielectric loss factor in these inventions is <0.007. The newly produced material samples described therein meet this requirement, although not significantly below it, so this prior art leaves considerable room for improvement, as the material is significantly away from the dielectric properties of polytetrafluoroethylene, which achieves a dielectric loss factor in the range of 0.0001. Since complete shielding of the polarity of the Si-O-Si backbone units in polyorganosiloxanes with a three-dimensional backbone structure is impossible, this structural element becomes an inherent disadvantage of polyorganosiloxanes and will always be a barrier to them, thereby achieving a lower dielectric loss factor.
[0008] For example, attempts to replace part of the polyorganosiloxane backbone with other bridging units other than Si-O-Si units are described in US 3395168. However, these inventions have in common that a significant part of the polyorganosiloxane backbone is still retained.
[0009] US 6072016 teaches linear, condensation-crosslinked silylene polymers as part of condensation-cured silicone formulations. The linear, condensation-crosslinked silylene polymers described therein are themselves condensable due to hydrolyzable end groups. In principle, these linear, condensation-crosslinked silylene polymers may not contain Si-O-Si units; however, as expected, their curing produces polyorganosiloxanes in which some bonds between adjacent silicon atoms are different from Si-O-Si units, and the units bridging Si atoms are present in the form of Si-C bonds. In addition to silylene units, silylene polymers also contain silylene units, which are an inevitable side effect of preparing them by hydrosilylation of silylene units with ethylenically unsaturated end groups. Pure polysilylene cannot be obtained in this way, and is not taught in US 6072016. It should also be noted that the starting materials used for hydrosilylation in US 6072016 can only be obtained by metal-mediated coupling reactions, such as Grignard reactions or Wurtz couplings. Although these synthetic methods can be implemented on an industrial scale, they are still challenging and the overall cost and complexity of realizing the technology are therefore considerable, making the inevitable assumption that the lack of profit margins will compromise the technology or allow it to break through only in markets where prices are extremely high and therefore volumes are very low. As for the dielectric properties, the likelihood is that, due to the platinum residues in the product from the hydrosilylation, an increased dielectric loss factor can be expected, which means that additional steps will be required to enable the technology (which is in any case already expensive and inconvenient) to be used for radiofrequency applications. In other words, the prior art according to US 6072016 will first have to be further developed in order to be able to be used industrially in the applications targeted by the present invention, in addition to the additional economic disadvantages it causes.
[0010] US 10982053 describes polymers containing linear aliphatic polyethers modified with silylene units. The polymers described here can carry phenol or epoxy groups. The copolymers are obtained by hydrosilylation of olefinically unsaturated polyethers with Si-H-functional silylene units. According to the teaching of US 10982053, pure silylene polymers cannot be obtained. The basic structural unit of the polymers according to US 10982053 is a polyether unit.
[0011] US 2011 / 0275768 gives a teaching similar to US 10982053, wherein the organic units located between the individual silanylene units are different from the polyether units according to US 10982053. In the case of US 2011 / 0275768, organosilicon polymers consisting only or predominantly of silanylene units are also not covered by the subject matter of the teaching described therein.
[0012] EP 0913420 teaches silylene silene polymers with an alternating structure, which are obtained by hydrosilylation of olefinically unsaturated silylene units with Si-H-terminal silylene units, similar to US 6072016. The profitability is subject to the same statements as already stated in US 6072016. Here too, expensive and complex metal-mediated coupling reactions are required to prepare the required raw materials. Only in this way can the hydrosilylation take place, and due to the use of platinum catalysts, it is itself an expensive synthesis. Platinum remains in the product and increases the dielectric loss factor. In order to obtain dielectric properties with radio frequency compatibility, the platinum must first be removed. This would require further steps and improvements to the prior art of EP 0913420, which go beyond the teaching of EP 0913420.
[0013] In the copolymers according to EP 0913420, as indicated by the fact that the polymers are designated as silanylenesilanylene polymers, there is a regular alternation of phenylene and alkylene bridges. This is unavoidable, considering that the vinyl groups required for polymer synthesis (which become bridged alkanediyl units by hydrosilylation with Si-H units) often alternate with phenylene units in the finished polymer backbone. As mentioned above, the phenylene units bridging Si atoms can only be obtained by metal-mediated coupling reactions, whether these reactions are Grignard reactions or Wurtz reaction-type couplings. Therefore, in the silanylene-silanylene copolymers according to EP 0913420, 50% of the bridging groups bridging adjacent Si atoms are arylene groups and 50% are alkylene or alkanediyl groups. Since the starting units used have only double symmetrical functionalization, high molecular weight linear polymers terminated with the remaining Si-H and / or olefinic groups are obtained. Here, instead of the silylene units with double olefinic unsaturation, pure organic starting units with double hydrosilylation ability, such as dienes or acetylene, can also be used. The silylenesilylene polymers described therein have sufficient solubility to be used for target applications as coating materials as long as there is a minimum fraction of 20 mol% of phenyl substituents bonded to silicon. Silylene polymers with random structures are neither described in EP 0913420 nor obtained by the method described in EP 0913420. Therefore, the structural chemistry obtainable according to this prior art is very limited. Therefore, EP 0913420 does not teach the general approach to obtain any desired silylene polymers. It is inevitable to use aliphatic units in silylene-silylene copolymers according to EP 0913420. It is known that the thermal stability obtained with aliphatic silicon-bonded units is lower than the thermal stability obtained with aromatic silicon-bonded groups. If the silylene units in the silylene-silylene copolymers of EP 0913420 are replaced by siloxane units, high thermal stability can be achieved, as described in the already cited prior art section. However, since this leads to disadvantages in terms of the achievable dielectric properties, the known prior art always leads to reduced thermal stability or reduced performance capacity in terms of dielectric properties. The combination of high thermal strength as expected for pure silylene polymers and the best electrical insulation properties obtainable in an economical process is not yet available from the existing prior art. This is the object proposed by the present invention.
[0014] US 9751989 teaches condensation-crosslinkable polyorganosiloxanes with oligomeric silphenylene units for use as materials for encapsulating LEDs. US 2017 / 051114 teaches hydrosilylation-curable formulations containing Si-H-terminated oligomeric silphenylenes and alkenyl-functional polyorganosiloxanes. In both cases, under the intended use, the final product is a polyorganosiloxane containing polyorganosiloxane units and oligomeric silphenylene units. Ethylenically unsaturated, free-radical-curable silphenylene polymers are not part of the teaching of these two specifications. Summary of the invention
[0015] The object of the present invention is to provide polymers which are crosslinkable by free-radical polymerization, which combine the advantageous properties of three-dimensionally crosslinkable polyorganosiloxanes, such as excellent heat resistance, weathering stability, water resistance and flame retardancy, have improved dielectric properties, more particularly a lower dielectric loss factor, and which are suitable for use as adhesives for metal-faced laminates for electronic applications and are economically obtainable.
[0016] Some of these are that in the form of pure adhesives, at 10 GHz, they have a dielectric loss factor of no more than 0.0030, effectively wet any fillers present which reduce the dielectric loss factor, allow the production of tack-free prepregs, produce formulations that are compatible with organic polymers, are easily cured under the action of heat to give dimensionally stable moldings, and have good solubility in typical application solvents. This object is achieved by the present invention.
[0017] The subject of the present invention is a silylene polymer of formula (I)
[0018] R a R 1 b Si[Y[(SiR 2 c R 3 d ) e ] f ] g YjY a R 1 b (I)
[0019] in
[0020] R may be identical or different and is a hydrogen radical or an olefinically or acetylenically unsaturated aliphatic or alicyclic hydrocarbon radical,
[0021] R 2 are independently the same or different groups, wherein R 2 It may be a hydrogen radical or a saturated or olefinically or acetylenically unsaturated, Si-C bonded C1 -C 18 Hydrocarbon radicals, in which oxygen atoms and silicon atoms are preferred as heteroatoms, wherein the same radical R 2 The two or more oxygen atoms in a group R are always separated from one another by a hydrocarbon unit, and if two heteroatoms are present simultaneously in one group R 2 In the case of the same group R 2 Two or more Si atoms in the cation may be joined to each other by direct Si-Si bonds, and the Si atoms are always tetravalent, and the remaining valences of the Si atoms are saturated by additional Si-C bonded substituents, preferably C 1-12 alkyl, cycloalkyl or aryl saturated, these may be olefinically or acetylenically unsaturated,
[0022] And R 2 It may also include olefinic or acetylenic unsaturated functional groups, which may also contain heteroatoms, wherein R 2 It may also be a hydroxyl group or a monovalent aliphatic, alicyclic or aromatic, Si—C-bonded organic hydrocarbon group bonded to the silicon atom via an oxygen atom, which is unsubstituted or substituted by heteroatoms and has 1 to 18 carbon atoms.
[0023] Group R 2 It may also be, in particular, a group of the formula (II) [Y[(SiR 2 c R 3 d ) e ] f ] g YjY a R 1 b , where Y, R, R 1 , R 2 , R 3 , a, b, c, d, e, f and g have the definitions given herein.
[0024] R 1 and R 3 are independently identical or different radicals and are a hydrogen radical or a monovalent aliphatic, alicyclic or aromatic, Si-C-bonded organic hydrocarbon radical which is unsubstituted or substituted by heteroatoms and has 1 to 18 carbon atoms and which may also be an unsaturated hydrocarbon radical, wherein R 1 and R 3 It may also be a hydroxyl group or a monovalent aliphatic, alicyclic or aromatic, Si-C-bonded organic hydrocarbon group which is bonded to the silicon atom via an oxygen atom, is unsubstituted or substituted by heteroatoms and has 1 to 18 carbon atoms.
[0025] It is a proviso of the present invention that each silylene polymer of formula (I) must always have at least one olefinically or acetylenically unsaturated group R, R 1 , R 2 or R 3 Each silylene polymer of formula (I) preferably has at least two such olefinically or acetylenically unsaturated groups R, R 1 , R 2 or R 3 Here, the olefinically or acetylenically unsaturated groups R and R 1 Always bonded at the terminal end; olefinically or acetylenically unsaturated group R 2 and R 3 Always bonded to a Si atom located inside (i.e., inside) the polymer backbone. There is no particular restriction on whether the olefinic or acetylenic unsaturated group is present at the end or inside. Both are possible, optionally also as a hybrid form. However, a condition of the present invention is that preferably at least two olefinic or acetylenic unsaturated groups are present on different Si atoms and are not bonded to the same Si atom.
[0026] Regarding the groups R and R bonded to oxygen 1 , R 2 and R 3 The number of groups R, R 1 , R 2 and R 3 The sum of all organic groups bonded to Si atoms through oxygen atoms may be no more than 10 mol%, more preferably no more than 8 mol%, more particularly no more than 5 mol%, and particularly preferably less than 1 mol%. The fact that should be considered here is that in the silylene polymer of formula (I) of the present invention, groups bonded to Si atoms through oxygen atoms are undesirable. They do not contribute to the improved performance capabilities of the silylene polymer of the present invention, on the contrary, they lead to reduced performance capabilities. Therefore, it is most preferred that there are no groups bonded to Si atoms through oxygen atoms in the silylene polymer of the present invention. However, due to secondary reactions in the synthesis process, the formation of such free radicals cannot always be completely suppressed. Therefore, a limited amount is allowed according to the present invention, but it is not preferred. The best performance capacity is achieved when any Si-O bond in the silylene polymer of the present invention is completely avoided.
[0027] The silylene polymer of the present invention preferably contains less than 10 mol% of silicon-oxygen-linked structural groups, more preferably less than 8 mol% of silicon-oxygen-linked structural groups, more particularly less than 5% of silicon-oxygen-linked structural groups, and particularly preferably less than 1% of silicon-oxygen-linked structural groups. The Si-O-linked structural groups herein refer not only to Si-O-Si backbone units, but also to Si-O units in which the oxygen atom is bonded to the silicon atom only on one side and the second oxygen-bonded group is not bonded to oxygen through the silicon atom. More particularly, it is preferred that the silylene polymer of the present invention does not contain Si-O-Si units. The silylene polymer of the present invention can be blended with polyorganosiloxanes and / or polysiloxane-polysilylene copolymers and / or organic polymers, and can be optionally used together with them if such use is advantageous for the selected application. Such mixtures, as well as those containing the silylene polymer of the present invention plus organic polymers, additives, fillers, pigments, etc., are also according to the present invention.
[0028] Y is a chemical bond or a di- to dodecavalent aromatic, alkylaromatic or cycloalkylaromatic or di- to dodecavalent aliphatic or alicyclic radical having 1 to 48 carbon atoms and whose main chain contains no heteroatoms, so that the main chain thus has, for example, no ether or polyether structure, which structure may optionally be present only as a side group bonded to the main chain, wherein Y may also contain olefinic or acetylenic unsaturated functional groups which, in addition to carbon atoms, may also contain heteroatoms such as N, P, O and S atoms, wherein oxygen atoms are particularly preferred as heteroatoms in the functional groups, excluding the presence of two or more oxygen atoms directly bonded to one another.
[0029] If group Y is not a chemical bond, it is always bonded to the silicon atom of its bridge by Si-C bond.Y is preferably di- to dodecavalent aromatics, alkyl aromatics, cycloalkyl aromatic groups.The condition of the present invention is that there is always such di- to dodecavalent aromatics, alkyl aromatics and cycloalkyl aromatic groups more than di- to dodecavalent aliphatic or alicyclic groups, and di- to dodecavalent aliphatic or alicyclic groups are randomly alternated and not alternated in regular order with di- to dodecavalent aromatics, alkyl aromatics, cycloalkyl aromatic groups.This also means that di- to dodecavalent aromatic groups, alkyl aromatic groups, cycloalkyl aromatic groups and di- to dodecavalent aliphatic groups or alicyclic groups can exist in blocks, and in each case are respectively composed of di- to dodecavalent aromatic groups, alkyl aromatic groups, cycloalkyl aromatic groups or di- to dodecavalent aliphatic groups or alicyclic groups of more number.
[0030] Another condition imposed on the silphenylene polymers of the present invention is that there is always a greater number of groups Y as divalent to dodecavalent aromatic, alkyl aromatic and cycloalkyl aromatic groups than groups Y as chemical bonds. Based on all bridging groups Y as 100 mol %, at least 55 mol % are groups Y as divalent to dodecavalent aromatic, alkyl aromatic and cycloalkyl aromatic groups, preferably at least 60 mol %, more preferably at least 70 mol %, more particularly at least 80 mol %. In a particularly preferred form of the present invention, all groups Y are those which are divalent to dodecavalent aromatic, alkyl aromatic and cycloalkyl aromatic groups.
[0031] The silylene polymer of the present invention has an arbitrary composition, i.e., a random composition. The condition of a random composition is automatically achieved by the synthetic method used, and is not conducive to the formation of silylene polymers with regularly alternating aromatic units, wherein the aromatic units contain groups Y with aliphatic or alicyclic groups Y.
[0032] Two or more radicals Y may have their definitions independently of one another, so that in the silphenylene polymer of formula (I), two or more radicals Y may be different radicals within the scope of the definitions indicated.
[0033] The index is defined as follows:
[0034] a is a number having a value of 1 or 2, preferably 1.
[0035] b is a number having a value of 1 or 2, preferably 2, wherein the sum of a+b=3.
[0036] c is a number with value 0, 1 or 2,
[0037] d is a number with a value of 0, 1, or 2, where the sum of c+d=2.
[0038] e is a number from 1 to 12, preferably from 1 to 6, more preferably from 1 to 3, and more particularly 1. If [(SiR 2 c R 3 d ) e ] where e is a number greater than 1, then the formula (SiR 2 c R 3 d ) are bonded to each other via Si-Si bonds to produce a disilane unit, a trisilane unit, etc., up to a polysilane unit depending on the value of e.
[0039] f is a number having a value from 1 to 12, more specifically 1.
[0040] g is a number having a value of 3-250, more preferably 4-150, and more particularly 5-50.
[0041] Examples of radicals R except hydrogen atoms are alkenyls, such as 7-octenyl, 5-hexenyl, 3-butenyl, allyl and vinyl. Also included are acryloyloxy or methacryloyloxy groups from acrylic acid or methacrylic acid, and acrylates or methacrylates of straight or branched alcohols having 1 to 15 carbon atoms. Preferred such radicals are those derived from methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, propyl acrylate, propyl methacrylate, n-butyl acrylate, n-butyl methacrylate, isobutyl acrylate, isobutyl methacrylate, tert-butyl acrylate, tert-butyl methacrylate, 2-ethylhexyl acrylate and norbornyl acrylate. Particularly preferred are methyl acrylate, methyl methacrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, 2-ethylhexyl acrylate and norbornyl acrylate. These groups are preferably not bonded directly to the silicon atom but rather via a hydrocarbon spacer which may contain 1 to 12 carbon atoms, preferably 1 or 3 carbon atoms and no heteroatoms other than those present in the acryloyloxy and / or methacryloyloxy groups.
[0042] In addition to hydrogen atoms, the group R 1 , R 2 and R 3 Examples are saturated or unsaturated hydrocarbon radicals which may contain aromatic or aliphatic double bonds, for example alkyl radicals such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, neopentyl and tert-pentyl; hexyl radicals such as n-hexyl; heptyl radicals such as n-heptyl; octyl radicals such as n-octyl and isooctyl radicals such as 2,2,4-trimethylpentyl and 2-ethylhexyl; nonyl radicals such as n-nonyl; decyl radicals such as n-decyl; dodecyl radicals such as n-dodecyl; tetradecyl radicals such as n-tetradecyl ; hexadecyl, such as n-hexadecyl; and octadecyl, such as n-octadecyl; cycloalkyl, such as cyclopentyl, cyclohexyl and 4-ethylcyclohexyl; cycloheptyl, norbornyl and methylcyclohexyl; aryl, such as phenyl, biphenyl, naphthyl and anthracenyl and phenanthryl; alkylaryl, for example o-tolyl, m-tolyl and p-tolyl, xylyl and ethylphenyl; aralkyl, such as benzyl; alkenyl, such as 7-octenyl, 5-hexenyl, 3-butenyl, allyl and vinyl, as well as α- and β-phenylethyl.
[0043] Can be present in the group R 1 , R 2 and R 3 A preferred heteroatom in is an oxygen atom.
[0044] Furthermore, a nitrogen atom, a phosphorus atom, a sulfur atom and a halogen atom such as a chlorine atom and a fluorine atom are also possible but not preferred.
[0045] Preferred heteroatom-containing organic groups R 1 , R2 and R 3 Examples of are acryloyloxy and methacryloyloxy groups from acrylic acid or methacrylic acid, respectively, and acrylates or methacrylates of unbranched or branched alcohols having 1 to 15 carbon atoms. Preferred groups of this type are those derived from methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, propyl acrylate, propyl methacrylate, n-butyl acrylate, n-butyl methacrylate, isobutyl acrylate, isobutyl methacrylate, tert-butyl acrylate, tert-butyl methacrylate, 2-ethylhexyl acrylate, and norbornyl acrylate. Particularly preferred are methyl acrylate, methyl methacrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, 2-ethylhexyl acrylate, and norbornyl acrylate.
[0046] These groups are preferably not bonded directly to the silicon atom, but rather via a hydrocarbon spacer which may contain 1 to 12 carbon atoms, preferably 1 or 3 carbon atoms, and contains no heteroatoms other than those contained in the acryloyloxy and / or methacryloyloxy groups.
[0047] Group R 1 , R 2 and R 3 Preference is given to acrylic acid esters or methacrylic acid esters selected from the group consisting of methyl, phenyl, vinyl, acryloyloxy and methacryloyloxy groups, and straight-chain or branched alcohols having 1 to 15 carbon atoms.
[0048] Further preferred heteroatom-containing groups R 1 , R 2 and R 3 are those of formula (III).
[0049]
[0050] In formula (III), R 4 , R 5 , R 6 , R 7 , R 8 and R 9 are independently a hydrogen group, a hydrocarbon group or a hydrocarbon group substituted by a foreign atom, wherein the group R 4 , R 5 , R 6 , R 7 , R 8 and R 9 There is always at least one hydrocarbon group bonded to the silicon atom via a Si-C bond, wherein the hydrocarbon group via which the group of formula (III) is bonded to the silicon atom is preferably a C3 hydrocarbon group containing no heteroatoms. Alternatively, the group R 4 , R 5 , R6 , R 7 , R 8 and R 9 It may also be a chemical bond, such that the group of formula (III) is directly bonded to the silicon atom via a Si—C bond to the aromatic ring.
[0051] Group R 4 , R 5 , R 6 , R 7 , R 8 and R 9 Examples are hydrogen radicals, saturated hydrocarbon radicals such as methyl, ethyl, n-propyl, isopropyl, primary, secondary and tert-butyl, hydroxyethyl, aromatic radicals such as phenethyl, phenyl, benzyl, methylphenyl, dimethylphenyl, ethylphenyl, heteroatom-containing radicals such as hydroxymethyl, carboxyethyl, methoxycarbonylethyl and cyanoethyl, and acrylate and methacrylate radicals such as methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, propyl acrylate, propyl methacrylate, n-butyl acrylate, n-butyl methacrylate, isobutyl acrylate, isobutyl methacrylate, tert-butyl acrylate, tert-butyl methacrylate, 2-ethylhexyl acrylate and norbornyl acrylate, and olefinically or acetylenically unsaturated hydrocarbon radicals.
[0052] Adjacent group R 4 and R 6 and the adjacent group R 5 and R 7 They may also be optionally linked to each other to form corresponding cyclic saturated or unsaturated groups to produce fused polycyclic structures.
[0053] Examples of phenolic groups of formula (III) are a phenol group, an o-, m- or p-cresol group, a 2,6-, 2,5-, 2,4- or 3,5-dimethylphenol group, a 2-methyl-6-phenylphenol group, a 2,6-diphenylphenol group, a 2,6-diethylphenol group, a 2-methyl-6-ethylphenol group, a 2,3,5-, 2,3,6- or 2,4,6-trimethylphenol group, a 3-methyl-6-tert-butylphenyl group, a thymol group and a 2-methyl-6-allylphenol group, which may optionally be substituted on the oxygen atom.
[0054] Preferred examples of the fluorine-containing group are trifluoropropyl, nonafluorohexyl and heptadecafluorooctyl groups.
[0055] Y is preferably a bridging organic unit having 1 to 24 carbon atoms, preferably an aromatic unit, which is between 2 and 12 carbosilyl units. Y is preferably divalent, trivalent or tetravalent, more particularly divalent.
[0056] Preferred bridging aromatic groups Y are those of the formulae (IVa), (IVb) and (IVc)
[0057]
[0058] The group R 10 , R 11 , R 12 and R 13 It may be a hydrogen radical or an optionally substituted hydrocarbon radical or a radical of the formula OR 14 A group in which R 14 Here, the adjacent groups such as R in formula (IVa) 10 and R 12 or R 11 and R 13 can be coupled to each other to form cyclic groups, resulting in fused ring systems. Similar comments apply to adjacent groups in formulae (IVb) and (IVc).
[0059] Typical examples of such bridging aromatic groups are p-, m- or o-phenylene, 2-methyl-1,4-phenylene, 2-methoxy-1,4-phenylene, particular preference being given to p-phenylene.
[0060] Optionally, two or more such groups can also be coupled to one another, so that, for example, two or more units of the formulae (IVa), (IVb) and (IVc) are coupled to one another and the oligomeric bridging structural element is present via the connection of the corresponding carbon atom of the terminal aromatic ring to the silicon atom. Hybrid forms are also conceivable here, in other words, oligomeric bridging units which consist not only of one unit of the formulae (IVa), (IVb) or (IVc), but instead of two or more, i.e. two or three different kinds of repeating units of the formulae (IVa), (IVb) and (IVc). In this case, the aromatic units can be directly bonded to one another, or they can be coupled to one another via bridging groups such as alkanediyl units, for example methylene, 1,2-ethanediyl, 1,1-ethanediyl, 2,2-dimethylpropyl or sulfone groups.
[0061] Other examples of aromatic bridging units which may also contain heteroatoms are those in which two optionally substituted phenolic rings are bridged via an alkanediyl or other unit. Typical representatives are -2,2-bis(4-hydroxyphenyl)propane groups substituted on the phenolic oxygen (substituted bisphenol A groups), 2,2-bis(4-hydroxyphenyl)methane groups (substituted bisphenol F groups), bis(4-hydroxyphenyl)sulfone groups (bisphenol S groups), in which the phenolic oxygen atom is usually replaced by -(C 3 H 6 )-type group substitution, wherein -(C 3 H 6 The )- group is bonded to the silicon atom in a silicon-carbon manner, thereby creating a bridge.
[0062] Preferred groups Y which are not bridged by aromatic units are, apart from the chemical bond, alkanediyl, alkenediyl and alkynediyl groups which may optionally contain heteroatoms and may contain aromatic groups as substituents but do not assume or contribute to a bridging function in these groups.
[0063] Typical examples are methylene, methine, tetravalent carbon, 1,1- and 1,2-ethanediyl, 1,4- and 1,3-butanediyl, 1,5-pentanediyl, 1,6-hexanediyl, 1,7-heptanediyl, 1,8-octanediyl, 1,9-nonanediyl, 1,10-decanediyl, 1,11-undecanediyl and 1,12-dodecanediyl, 1,2-diphenylethanediyl, 1,2-phenylethanediyl, 1,2-cyclohexylethanediyl. In the case where the linear bridging unit has more than one carbon atom and the substitution pattern permits it, each of these groups can also be linked not only via α-ω, in other words via a bridge via the respective first and last atoms of the linear unit, but also via any other connection, in other words using other chain carbon atoms to play its bridging role. Furthermore, typical examples are not only the linear representatives of the bridging hydrocarbons mentioned, but also their isomers, which in turn can exert their bridging effect via the connection of different carbon atoms of the hydrocarbon structure to the silicon atom.
[0064] An example of a particularly preferred group from the group consisting of nonaromatic hydrocarbon groups containing no heteroatoms is -CH 2 CH 2 -、-CH(CH 3 )-、-CH=CH-、-C(=CH 2 )-and -C≡C-.
[0065] An example of a typical fluorine-substituted bridging group Y is -C(CF 3 ) 2 -, -C(H)FC(H)F- and -C(F 2 )-C(F 2 )-group.
[0066] Examples of typical heteroatom-containing non-aromatic bridging groups are divalent hydrocarbon groups containing secondary or tertiary alcohol functions, ketone and carboxylic acid and ester functions or having side ether chains. Here, side groups mean that the corresponding group has its origin in a carbon atom of the group Y, but the end of the group is not bonded to a Si atom, which is bonded to another Si atom via a bridging group. As a result, the group does not contribute to the network structure.
[0067] All statements are to be construed as illustrative only and not restrictive.
[0068] As described below, a preferred method for preparing the silphenylene polymers of the invention consists in applying the synthesis by means of a Grignard reaction. Groups which are listed here as examples but which are not inert toward magnesium will not be tolerated in such a reaction and are converted accordingly. However, in order to obtain them in the silphenylene polymers of the invention, the groups used in the Grignard reaction are initially only those which are inert toward magnesium and which, according to the known prior art, are generated in the subsequent reaction in the precursor obtained by the Grignard reaction. Examples of such groups are carbonyl-containing groups, such as acryloyloxy or methacryloyloxy.
[0069] The viscosity of the silphenylene polymers of the present invention may vary within a wide range, or may be solid, depending on the average number of structural units forming them per molecule.
[0070] The liquid silphenylene polymer of the present invention in the non-crosslinked state has a viscosity of 20 to 8,000,000 mPas, preferably 200 to 5,000,000 mPas, more particularly 250 to 3,000,000 mPas at 25°C.
[0071] The solid silphenylene polymer of the present invention in a non-crosslinked state has a glass transition temperature in the range of 25°C to 250°C, preferably 30°C to 230°C, more particularly 30°C to 200°C.
[0072] The silylene polymers of the present invention can in principle be obtained by any method that leads to the formation of a bond between a Si atom and a carbon atom. Typical representatives of such reactions are Grignard reactions, coupling reactions in the manner of Wurtz synthesis (optionally adapted in the synthesis scheme) and hydrosilylation reactions. All these types of reactions are essentially prior art and are therefore known to those skilled in the art. For a basic overview of not only these but also other organometallic reactions for forming Si-C bonds, reference is made to the silicon chemistry module of the University of Freiburg, which can be obtained using the following link: https: / / tu- freiberg.de / sites / default / files / media / institut-fuer-anorganische-chemie- 10441 / lehre / kroke / siliciumchemie5.pdf
[0073] Tips and information about the Grignard synthesis method can be found, for example, in Synthesis of Silphenylene-Containing Siloxane Resins Exhibiting Strong Hydrophobicity and High Water Vapor Barriers, Xunjun Chen, Minghao Yi, Shufang Wu, Lewen Tan, Yixin Xu, Zhixing Guan, Jianfang Ge, and Guoqiang Yin, Coatings, 2019, 9, 481.
[0074] In order to prepare the silphenylene polymers of the present invention, reaction conditions and appropriate selection of starting materials must be observed.
[0075] As already pointed out in the discussion of the prior art, hydrosilylation reaction is not preferred for the preparation of the silylene polymer of the present invention. EP 0913420 lists the raw materials required for the hydrosilylation reaction for obtaining the silylene-silylene polymer described in EP 0913420. These are disilphenylene and silylene with olefinic unsaturated ends, or diunsaturated silanes. The corresponding silylene raw materials can be obtained by Grignard reaction again. In the case of the silylene polymer of the present invention, this is not any different. This means that, relative to Grignard synthesis or Wurtz synthesis or any other procedures that directly provide the silylene polymer of the present invention, hydrosilylation represents the disadvantages caused by the additional steps, the increased cost and complexity and the thus reduced profitability. In addition, in the case of the present invention, there is no structural element of regular alternation in the polymer backbone, as in the case of EP 0913420, the polymer has a random composition instead, for a successful hydrosilylation route to the silylene polymer of the present invention and the possible specific synthesis strategy that allows the composition according to the present invention, a relatively large amount of suitable raw materials will be required. Overall, therefore, although the hydrosilylation reaction is in principle suitable for obtaining the silphenylene polymers of the present invention, it requires considerable additional costs and complexity relative to methods such as the Wurtz or Grignard synthesis.
[0076] Therefore, in contrast to the silphenylene-silanylene polymers and silphenylene-siloxane copolymers described in the known prior art, the hydrosilylation reaction is not preferred as a synthetic route for the silphenylene polymers of the invention. The new state of the art described here is achieved at most by a process that differs from the preferred process according to the known prior art.
[0077] A preferred method for preparing the silphenylene polymers of the invention comprises forming magnesium-mediated Si-C bonds by means of a Grignard reaction. By this method, the silphenylene polymers of the invention can be obtained in a single process step and thus with the desired purity with the greatest yield.
[0078] For the preferred method of preparing the silphenylene polymers of the present invention, silicon-containing compounds of formula (IV), (V) and (VI) are used,
[0079] R 15 h R 16 i Si (IV),
[0080] R 15 j R 16 k Si[SiR l 17 R m 18 ] n S i j 15 R k 16 (V),
[0081] R 15 j R 16 k Si[SiR l 17 R m 18 ] n -X 1 -[SiR l 17 R m 18 ] n S i 15 j R 16 k (VI)
[0082] Where R 15 is a halogen atom or a C1-C3 alkoxy group, preferably a chlorine, bromine or iodine atom or a methoxy group, more particularly a Cl atom or a methoxy group, wherein two or more radicals R 15 may be a group different from the groups mentioned; in particular, two or more groups R in the same molecule 15 May be a halogen group and an alkoxy group, and
[0083] R 16 , R17 and R 18 can be independently selected from the group R, R 1 , R 2 or R 3 , but not a group of formula (II), and R 18 may additionally be a halogen group or a C1-C3 alkoxy group, wherein the group R 16 , R 17 and R 18 does not contain a functional group comprising a carbonyl or carboxyl group, a hydroxyl group, a double-bonded nitrogen atom, a primary, secondary or tertiary amine group or a thiol group, such that the group R 16 , R 17 and R 18 Inert to magnesium.
[0084] X 1 is a chemically bonded or magnesium-inert divalent bridged aliphatic, cycloalkyl aliphatic, cycloalkyl aromatic or alkyl aromatic hydrocarbon radical which does not contain a functional group comprising a carbonyl or carboxyl group, a hydroxyl group, a double-bonded nitrogen atom, a primary, secondary or tertiary amine group or a thiol group and is represented by the formula R 19 -X 2 -R 19 Hydrosilylation of a hydrosilylatable olefinically or acetylenically unsaturated precursor Z produces 19 is an olefinically or acetylenically unsaturated hydrosilylatable C2-C8 group, and X 2 is a group X shortened on either side by C2-C8 1 . Cycloaliphatic, cycloaromatic or aromatic hydrocarbon group X 2 Examples are those already described for Y, with the limitation that for X 2 , the only groups from the group of radicals Y which are permitted are those which are inert towards magnesium.
[0085] h is an integer having a value of 1, 2, 3 or 4, preferably 1, 2 or 3
[0086] i is an integer having a value of 0, 1, 2 or 3 and the sum of h+i=4.
[0087] j is a number having a value of 0, 1, 2 or 3, wherein j at least at one terminal Si atom of the disilane, oligosilane or polysilane of formula (V) has a value of 1, and at least one radical R is always present per molecule of formula (V) 15 ,
[0088] k is an integer with a value of 0, 1, 2 or 3, where k+j=3.
[0089] l and m are each numbers having a value of 0, 1 or 2, where l+m=2.
[0090] n is a number with a value of 0-50, preferably 0-30.
[0091] Compounds of formula (VI) containing a group X bonded to the adjacent Si atom by hydrosilylation 1 , preferably obtained by hydrosilylation of the precursor Z with a Si-H-functional silicon-containing compound of formula (VII)
[0092] R 15 j R 16 k Si[SiR l 17 R m 18 ] n -H(VII),
[0093] Where R 15 , R 16 , R 17 and R 18 and j, k, l and m have the above definitions and H is a hydrogen atom. For n=0, (VII) is a halosilane or alkoxysilane; for n>0, (VII) is a halogenated or alkoxylated disilane, oligosilane or polysilane. Hybrid forms are also conceivable, in which case R 15 In the same molecule there are both halogen groups and alkoxy groups.
[0094] In addition to starting materials for preparing compounds of formula (VI), compounds of formula (VII) can also be used for preparing the silphenylene polymers of the invention, in which case they can participate via the halogen groups and / or alkoxy groups in the Grignard reaction preferably used for preparing the silphenylene polymers of the invention.
[0095] Typical examples of silanes of the general formula (IV) are methyltrichlorosilane, methyltrimethoxysilane, methyltriethoxysilane, dimethyldichlorosilane, dimethyldichlorosilane, dimethyldiethoxysilane, trimethylchlorosilane, trimethylmethoxysilane, trimethylethoxysilane, trimethylsilanol, phenyltrichlorosilane, phenyltrimethoxysilane, phenyltriethoxysilane, phenylmethyldichlorosilane, phenylmethyldimethoxysilane, phenylmethyldiethoxysilane, diphenyldichlorosilane, diphenyldimethoxysilane, diphenyldiethoxysilane, triphenylchlorosilane, triphenylmethoxysilane, triphenylethoxysilane, diphenylmethylchlorosilane. silane, diphenylmethoxysilane, diphenylmethyldiethoxysilane, phenyldimethylchlorosilane, phenyldimethylmethoxysilane, phenyldimethylethoxysilane, vinyltrichlorosilane, vinyltrimethoxysilane, vinyltriethoxysilane, vinyldimethylchlorosilane, vinyldimethylmethoxysilane and vinyldimethylethoxysilane, trichlorosilane, trimethoxysilane, triethoxysilane, methyldichlorosilane, methyldimethoxysilane, methyldiethoxysilane, dimethylchlorosilane, dimethylmethoxysilane, dimethylethoxysilane, ethyltrichlorosilane, ethyltrimethoxysilane, ethyltriethoxysilane and tetrachlorosilane. Particularly preferred silanes of formula (IV) are methyltrichlorosilane, methyltrimethoxysilane, dimethyldichlorosilane, dimethyldimethoxysilane, vinyltrichlorosilane, vinyltrimethoxysilane, vinyldimethylchlorosilane, vinyldimethylmethoxysilane, phenyltrichlorosilane, phenyltrimethoxysilane, phenylmethyldichlorosilane and phenylmethyldimethoxysilane. The silanes of formula (IV) can also be used in the form of a mixture. For example, a mixture of silanes is preferably used, which is used for chain formation and crosslinking, and is mixed with end-capping silanes. The description of the examples should be understood to be illustrative and not restrictive.
[0096] Typical examples of di-, oligo- and polysilanes of formula (V) are hexachlorodisilane, hexamethoxydisilane, hexaethoxydisilane, dimethyltetrachlorodisilane, dimethyltetramethoxydisilane, dimethyltetraethoxydisilane, trimethyltrichlorodisilane, trimethyltrimethoxydisilane, trimethyltriethoxydisilane, tetramethyldichlorodisilane, tetramethyldimethoxydisilane, tetramethyldiethoxydisilane, dimethylvinyltrichlorodisilane, dimethylvinyltrimethoxydisilane, dimethylvinyltriethoxydisilane, diphenyltetrachlorodisilane, diphenyltrimethoxydisilane, diphenyltetraethoxydisilane, diphenylvinyltrichlorodisilane, diphenylvinyltrimeth ... triethoxydisilane, tetravinyldichlorodisilane, tetravinyldimethoxydisilane, tetravinyldiethoxydisilane, divinyltetrachlorodisilane, tetravinyldimethoxydisilane, tetravinyldiethoxydisilane, trimethyldichlorodisilane, trimethyldimethoxydisilane, trimethyldiethoxydisilane, octachlorotrisilane, octamethoxytrisilane, octaethoxytrisilane, tetramethyltetrachlorotrisilane, tetramethyltetramethoxytrisilane, tetramethyltetraethoxytrisilane, hexamethyldichlorotrisilane, hexamethyldimethoxytrisilane, hexamethyldiethoxytrisilane, pentamethyltrichlorotrisilane, pentamethyltrimethoxysilane, pentamethyldiethoxytrisilane, diphenyldivinyltetrachlorotrisilane, diphenyldivinyl triethoxytrisilane, diphenyldivinyltetraethoxytrisilane, diphenyldimethylvinyltrichlorotrisilane, diphenyldimethylvinyltrimethoxysilane, diphenyldimethylvinyltriethoxytrisilane, tetramethyltrichlorotrisilane, tetramethyltrimethoxytrisilane, tetramethyltriethoxytrisilane, hexamethylchloromethoxytrisilane, hexamethylmethoxytrisilane, hexamethylethoxytrisilane, pentamethyldichlorotrisilane, pentamethyldimethoxytrisilane, pentamethyldiethoxytrisilane, diphenyldivinyltrichlorotrisilane, diphenyldivinyltrimethoxytrisilane, diphenyldivinyltriethoxytrisilane, diphenyldimethylvinyldichlorotrisilane, diphenyldimethylvinyldimethoxytrisilane , diphenyldimethylvinyldiethoxytrisilane, nonamethylnonachlorooctasilane, nonamethylnonamethoxyoctasilane, nonamethylnonaethoxyoctasilane, heptamethyldiphenylnonachlorooctasilane, heptamethyldiphenylnonamethoxyoctasilane, heptamethyldiphenylnonaethoxyoctasilane, heptamethyldiphenyldivinylheptachlorooctasilane, heptamethyldiphenyldivinylheptamethoxyoctasilane, heptamethyldiphenyldivinylheptaethoxyoctasilane, heptamethyltetraphenylheptachlorooctasilane, heptamethyltetraphenylheptamethoxyoctasilane, heptamethyltetraphenylheptaethoxyoctasilane, wherein methyl, phenyl, ethyl, vinyl and Si-H groups and chlorine and / or methoxy and ethoxy groups may be randomly distributed on the silicon atom, in accordance with the rule that each Si atom is tetravalent. The description should be understood as illustrative and not restrictive.Instead of Si atoms being substituted exclusively by Cl atoms or methoxy or ethoxy groups, representatives with mixed Cl, methoxy and / or ethoxy functions are also possible in the exemplary molecules of the formula (V) and likewise belong to typical examples.
[0097] Typical examples of di-, oligo- and polycarbosilanes of formula (VI) are
[0098] Cl(CH 3 ) 2 Si-CH 2 CH 2 -Si(CH 3 ) 2 Cl, Cl 2 (CH 3 )Si-CH 2 CH 2 -Si(CH 3 ) 2 Cl, Cl 2 (CH 3 )Si-CH 2 CH 2 -Si(CH 3 )Cl 2 , Cl 3 Si-CH 2 CH 2 -SiCl 3 ,
[0099] Cl(CH 3 ) 2 Si-CH=CH-Si(CH 3 ) 2 Cl, Cl 2 (CH 3 )Si-CH=CH-Si(CH 3 ) 2 Cl,
[0100] Cl 2 (CH 3 )Si-CH=CH-Si(CH 3 )Cl 2 , Cl 3 Si-CH=CH-SiCl 3 ,
[0101] Cl(CH 3 ) 2 Si-(CH 2 ) 3 (C 6 H 4 )(CH 2 ) 3 -Si(CH3 ) 2 Cl、Cl 2 (CH 3 )Si-(CH 2 ) 3 (C 6 H 4 )(CH 2 ) 3 -Si (CH 3 ) 2 Cl、Cl 2 (CH 3 )Si-(CH 2 ) 3 (C 6 H 4 )(CH 2 ) 3 -Si (CH 3 )Cl 2、 Cl 3 Si-(CH 2 ) 3 (C 6 H 4 )(CH 2 ) 3 -SiCl 3 、
[0102] Cl(CH 3 )Si-Si(CH 3 ) 2 -(CH 2 ) 3 (C 6 H 4 )(CH 2 ) 3 -(CH 3 ) 2 Si-Si (CH 3 ) 2 Cl
[0103] Cl(CH 3 ) 2 Si-(CH 2 ) 3 (C 6 H 4 )-(C 6 H 4 )(CH 2 ) 3 -Si (CH 3 ) 2 Cl、Cl 2 (CH 3 )Si-(CH 2 ) 3 (C6 H 4 )-(C 6 H 4 )(CH 2 ) 3 -Si (CH 3 ) 2 Cl、Cl 2 (CH 3 )Si-(CH 2 ) 3 (C 6 H 4 )-(C 6 H 4 )(CH 2 ) 3 -Si (CH 3 )Cl 2 、Cl 3 Si-(CH 2 ) 3 (C 6 H 4 )-(C 6 H 4 )(CH 2 ) 3 -SiCl 3 、
[0104] Cl(CH 3 ) 2 Si-CH 2 CH 2 -Si (CH 3 )(CH=CH 2 )Cl、Cl(CH 3 )(CH=CH 2 )Si-CH 2 CH 2 -
[0105] Si(CH 3 )(CH=CH 2 )Cl、Cl(CH 3 )(CH=CH 2 )Si-(CH 2 ) 3 (C 6 H 4 )(CH 2 ) 3 -Si (CH 3 )(CH=CH 2 )Cl、Cl(CH=CH 2 ) 2 Si-(CH 2 ) 3 (C6 H 4 )(CH 2 ) 3 -Si(CH=CH 2 ) 2 Cl, Cl(CH 3 )(H)Si-(CH 2 ) 3 (C 6 H 4 )(CH 2 ) 3 -Si(CH 3 )(H)Cl, Cl(H) 2 Si-(CH 2 ) 3 (C 6 H 4 )(CH 2 ) 3 -Si(H) 2 Cl,
[0106] In each case, instead of a chlorine atom, a methoxy or ethoxy group can be included in the exemplary molecules of formula (VI), and it is possible to also form representatives with mixed Cl, methoxy and / or ethoxy functional groups and likewise belong to typical examples. The description should be understood as illustrative and not restrictive.
[0107] Organic starting materials suitable for preparing the silylene groups of the present invention are those of formula (VIII)
[0108] [Hal] o -Y(VIII),
[0109] wherein Hal is a Cl, Br or iodine atom, preferably a Cl or Br atom, o is a number from 2 to 12, preferably 2, and Y has the definition indicated above for it.
[0110] Typical examples of organic starting materials of the formula (VIII) are derived from the description of examples of radical Y in which the free valencies are saturated by halogen atoms.Particularly preferred representatives of formula (VIII) are dihalobenzenes such as 1,4-dibromobenzene, 1,4-dichlorobenzene, 1,2-dichlorobenzene, 1,2-dibromobenzene, 1,2-dichloroethane, 1,2-dibromoethane, 1,1-dichloroethane, 1,1-dibromoethane, 1,4-dichlorobutane, 1,4-dibromobutane, 1,3-dichlorobutane, 1,3-dibromobutane, 1,5-dichloropentane, 1,5-dibromopentane, 1,6-dichlorohexane, 1,6-dibromohexane, 1,7-dichloroheptane, 1,7-dichlorobutane, 1,7-dibromobutane, 1,7-dichloroheptane, 1,7-dichlorobutane, 1,7-dibromobutane, 1,7-dichlorobutane, 1,7-dichlorobutane, 1,7-dibromobutane, 1,7-dichloropentane, 1,7-dibromopentane, 1,7-dichlorohexane, 1,7-dibromohexane, 1,7-dichloroheptane, 1,7-dichlorobutane, 1,7-dibromobutane, 1,7-dichlorobutane, 1,7-dibromobutane, 1,7-dichloropentane, 1,7-dibromopentane, 1,7-dichlorohexane, 1,7-dibromohexane, 1,7-dichloroheptane, 1,7-dichlorobutane, 1,7-dichlorobutane, 1,7-dibromobutane, 1,7-dichlorobutane, 1,7-dichlorobutane, 1,7-dichlorobutane, 1,7-dichlorobutane, 1, Bromoheptane, 1,8-dichlorooctane, 1,8-dibromooctane, 1,9-dichlorononane, 1,9-dibromononane, 1,10-dichlorodecane, 1,10-dibromodecane, 1,11-dichloroundecane, 1,11-dibromodecane, 1,12-dichlorododecane, 1,12-dibromododecane, 1,2-dichlorodiphenylethane, 1,2-dibromodiphenylethane, 1,2-dichlorocyclohexylethane, 1,2-dibromocyclohexylethane, 2-methyl-1,4-dichlorobenzene, 2-methyl-1,4-dibromo Benzene, 2-methoxy-1,4-dichlorobenzene, 2-methoxy-1,4-dibromobenzene, 2-ethyl-1,4-dichlorobenzene, 2-ethyl-1,4-dibromobenzene, 2-ethoxy-1,4-dichlorobenzene, 2-ethoxy-1,4-dibromobenzene, 2-n-propyl-1,4-dichlorobenzene, 2-n-propyl-1,4-dibromobenzene, 2-n-propoxy-1,4-dichlorobenzene, 2-n-propoxy-1,4-dibromobenzene, 2-isopropyl-1,4-dichlorobenzene, 2-isopropyl-1,4-dibromobenzene, 2-n-butyl -1,4-dichlorobenzene, 2-n-butyl-1,4-dibromobenzene, 2-sec-butyl-1,4-dichlorobenzene, 2-sec-butyl-1,4-dibromobenzene, 2-tert-butyl-1,4-dichlorobenzene, 2-tert-butyl-1,4-dibromobenzene, polyhalogenated biphenyls such as dibromobiphenyl, tribromobiphenyl, tetrabromobiphenyl, pentabromobiphenyl, hexabromobiphenyl, heptabromobiphenyl, octabromobiphenyl, nonabromobiphenyl, decabromobiphenyl and the corresponding polychlorinated biphenyl analogs, 4-chlorobenzyl chloride, 4-bromodiphenylmethane (4-bromobenzhydryl chloride bromide), diphenyldichloromethane, diphenyldibromomethane, 1,2-diphenyl-1,2-dichloroethane, 1,2-diphenyl-1,2-dibromoethane, 1,1'-(2,2,2-trichloroethane-1,1-diyl)bis(4-chlorobenzene), hexachlorocyclohexane, 1,2,4,5,6,7,8,8-octachloro-3a,4,7,7a-tetrahydro-4,7-methylene Indane (chlordane), 1,2,3,4,10,10-hexachloro-6,7-epoxy-1,4,4a,5,6,7,8,8a-octahydro-1,4-endo-5,8-epoxy-dimethylenenaphthalene (dieldrin), 1-bromo-4-chlorobenzene, 4,4'-(propane-2,2-diyl)bis(2,6-dibromophenol) (tetrabromobisphenol A), 3,5,3',5'-tetrachlorobisphenol A.
[0111] Preferred representatives of the formula (VIII) are 1,4-dibromobenzene, 1,4-dichlorobenzene, 1,2-dichloroethane and 1,2-dibromoethane. Mixtures of different representatives of the formula (VIII) may optionally be used.
[0112] Like all other descriptions of the typical examples, the descriptions are to be understood illustratively and not restrictively.
[0113] Magnesium as metal is conveniently used in a form having a large surface area, ie for example in the form of turnings, granules or powders. Magnesium is preferably used in the minimum amount specified by the following equation: p = (q / 2) + r.
[0114] Here, p represents the number of moles of magnesium, q represents the number of halogen and alkoxy equivalents from compounds (IV), (V), (VI), (VII) and (VIII), and r is a value between 0 and half of the respective used amount of halogen and alkoxy equivalents from compounds (IV), (V), (VI), (VII) and (VIII), excluding r values of 0. In other words, r is always greater than zero and has a maximum value of q / 2. Magnesium is used in excess relative to the number of halogen atoms and alkoxy groups.
[0115] To promote the reaction, a solvent inert to the reaction participants is used in the preferred process for preparing the silphenylene polymers according to the invention. In principle, substances which are typically used as inert solvents in the reaction of metals with organic halides can be used here, these being more particularly ethers, such as diethyl ether, di-n-butyl ether, tert-butyl methyl ether, tetrahydrofuran, 1,4-dioxane or hexamethylphosphoramide, which can also optionally be used in a mixture with one another and optionally in a mixture with further inert solvents such as toluene, xylene or ethylbenzene. In this case, however, it should be ensured that the solvent used is also inert to the reaction participants. It has been found, for example, that Si-Cl-containing components of the formulae (IV), (V), (VI) and (VII) react with THF in the case of ring opening to form butoxy groups which, when they are formed, are inserted into the silphenylene polymer by reaction and which form unwanted alkoxy groups which, in principle, react for hydrolysis to form silanol groups which in turn can undergo condensation to form likewise unwanted Si-O-Si units. As will be seen later, the water treatment operation optionally uses an acid such as hydrochloric acid, and therefore this reaction is possible during the treatment. This secondary reaction will produce silphenylene-polysiloxane copolymers which are not according to the invention.
[0116] In the prior art relating to the preparation of silphenylene-polysiloxane polymers containing polysiloxane units, for example according to US Pat. No. 3,350,350 A, this situation is not taken into account, since in this case the formation of siloxane units does not contradict the invention. However, in the case of the present invention, this is different and, in this context, in detail, is the novelty of the selected process for preparing the silphenylene polymers of the invention. In the case of the present invention, together with the Si-Cl-containing components of the formulae (IV), (V), (VI) and (VII), the only candidate solvents are those which are inert toward chlorosilanes, such as 1,4-dioxane and hexamethylphosphoramide. The use of THF, for example, is indeed possible, but only in conjunction with the alkoxy-functional components of the formulae (IV), (V), (VI) and (VII).
[0117] The preferred process for preparing the silphenylene polymers of the invention is preferably carried out at a temperature of from -78°C to 150°C at atmospheric pressure. Optionally, higher or lower pressures can also be used. The process is conveniently carried out in an atmosphere inert to the reaction participants, which atmosphere consists of nitrogen or argon, wherein the most likely practice is to exclude water from entering the container and onto the magnesium as a liquid, vapor or coating by applying suitable state-of-the-art measures, such as baking under reduced pressure.
[0118] The preferred process for preparing the silphenylene polymers of the invention is preferably carried out in stages, first reacting component (VIII) with magnesium and in a second step adding the desired selected components (IV), (V), (VI) and (VII) separately. However, the process can also be carried out in one step, wherein the component of formula (VIII) is reacted in the presence of the desired selected component selected from the group consisting of formula (IV), (V), (VI) and optionally (VII). In order to activate magnesium, it is advantageous to first combine a portion of component (VIII), for example 10% by weight of the total amount of component (VIII), with magnesium.
[0119] The reaction product obtained in the preferred method can be separated in the same manner as the reaction product obtained in the organometallic synthesis (especially the Grignard synthesis). The reaction mixture obtained is preferably mixed with water at 0 to 30 ° C. Since in this case, hydrochloric acid is formed by the Si-Cl groups that still exist, and silanol groups that lead to condensation and the formation of Si-O-Si units are generated, both of which are undesirable, before post-treatment, complete or very close to complete conversion of all halogen groups involved in the reaction should be ensured. This also applies to silicon-bonded alkoxy groups that still exist during the addition of water. These groups can also be hydrolyzed and form silanol groups that can condense. For this reason, in contrast to the prior art (e.g., Grignard-similar synthesis for preparing polysilylene arylsiloxanes according to US3350350 A), the amount of magnesium used in the present invention is not equal to the amount of halogen atoms and alkoxy groups used; on the contrary, an excess of magnesium is used. Optionally, one possibility is to use an acid for post-treatment, such as hydrochloric acid, to adjust the pH or promote the formation of magnesium halide.
[0120] The water-soluble salt components are subjected to water extraction, while solids such as possibly insoluble magnesium parts or magnesium salts are removed by state of the art methods such as by filtration or centrifugation.
[0121] The volatile components of the reaction mixture are removed by known techniques, such as continuous or batch distillation, to obtain the reaction products in pure form. If the reaction products are desired as preparations in solvents, they can be subsequently dissolved in the selected solvent or obtained directly as the desired preparation by solvent exchange from the reaction solvent. The solvent exchange is also carried out according to known prior art.
[0122] If it is desired to further modify the silphenylene polymer obtained as the main product by the preferred process, for example by introducing functional groups that are unstable to the Grignard synthesis conditions, it may be advantageous to introduce suitable functional groups into the main silphenylene polymer in a Grignard-analogous synthesis step. In this case, it should be borne in mind that the silphenylene polymer obtained mainly in this way already meets all the characteristics of the inventive step and is therefore in accordance with the invention. It is known from the prior art that the carbonyl groups of aldehydes, ketones and carboxylic acids and their esters are converted into alcohols by Grignard reactions. Therefore, if carbinol groups are desired for the subsequent introduction of functional groups, one possibility thereof would be to use, for example, a carbinol-functional starting material and to use a carbonyl- or epoxy-functional starting material by selecting a suitable component of formula (VIII). Since the Grignard reagent is consumed both in the presence of alcohols and in the reaction of the carbonyl group, the additional requirements of the Grignard reagent must be borne in mind. Considering that this method may jeopardize the economic viability of the method in some cases, this method is not preferred, although it is in principle possible and is therefore included in the present invention.
[0123] By the reaction of acryloyl, methacryloyl or chloropropionyl chloride with this carbonyl group, for example, acrylate groups or methacrylate groups can be introduced into the silphenylene polymers of the present invention. In the case of the reaction with the acyl chlorides of methacrylic acid and acrylic acid, the corresponding methacrylate or acrylate is formed after the elimination of HCl, which can optionally be promoted using suitable amines such as tertiary amines. In the case of chloropropionyl chloride, the product of the first step is the ester of chloropropionic acid, which is treated alkaline in the second step by using, for example, tertiary amines, and by eliminating HCl from the propionyl chloride group, an acrylic acid group is formed. All reactions are prior art and are therefore not new per se. However, their use for the preparation of the silphenylene polymers that are the subject of the present invention is novel, and therefore these steps are included within the scope of the present invention as components of the preferred method for preparing the silphenylene polymers of the present invention.
[0124] The silylene polymers of formula (I) all have at least olefinic or acetylenic unsaturated functional groups, through which they can be chemically crosslinked. Possible chemical crosslinking reactions in this context include known prior art reactions, more specifically free radical crosslinking, which can be initiated using suitable radiation sources such as UV light or by unstable compounds that decompose into free radicals, and addition crosslinking, for example by hydrosilylation of olefinic unsaturated groups with Si-H functional groups in the presence of suitable hydrosilylation catalysts. Si-H functional groups can also be combined with the silylene polymers of the present invention.
[0125] In order to achieve adequate curing, a sufficient amount of functional groups must be present. At least an average of 1.0 functional groups per molecule of the silicon phenylene polymer used in the present invention must be present to achieve adequate curing; preferably, an average of at least 1.1, more particularly an average of at least 1.2 functional groups are present per molecule of the silicon phenylene polymer of the present invention. The functional groups here can be different, for example, some functional groups are Si-H groups, while some other functional groups represent olefinically unsaturated groups that can be free radically cured or can be hydrosilylated. Other combinations of complementary functional groups are also conceivable, "complementary" meaning that the selected functional group combinations are capable of reacting with each other. If only one free radically curable functional group is present, for example, only functional groups with olefinic or acetylenic unsaturation, a corresponding number of these functional groups must be present. In the sense of copolymerization to form a uniform matrix, it should be ensured that sufficient copolymerizability is present on the selected part of the olefinic and acetylenic groups. Combinations of olefinic groups which are not copolymerizable with one another are also possible, provided that the matrix obtained comprising two or possibly more individual polymers remains compatible with one another and does not form individual phases which separate into distinguishable domains from one another.
[0126] Examples of suitable initiators for starting the free-radical polymerization include those from the field of organic peroxides, such as di-tert-butyl peroxide, dilauryl peroxide, dibenzoyl peroxide, dicumyl peroxide, cumyl peroxyneodecanoate, tert-butyl peroxyneodecanoate, tert-amyl peroxypivalate, tert-butyl peroxypivalate, tert-butyl peroxyisobutyrate, tert-butyl peroxy-3,5,5-trimethylhexanoate, tert-butyl cumyl peroxide, tert-butyl peroxyacetate, tert-butyl peroxybenzoate, 1,1-bis(tert-butylperoxy)cyclohexane, 2,2-di(tert-butylperoxy)butane, bis(4-tert-butylcyclohexyl)peroxydicarbonate, hexadecyl peroxydicarbonate, tetradecyl peroxydicarbonate, dibenzyl peroxydicarbonate, diisopropylbenzene, dihydroperoxides,
[0127] [1,3-phenylenebis(1-methylethylidene)]bis[tert-butyl]peroxide, 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexane, dihexadecyl peroxydicarbonate, acetylacetone peroxide, acetylcyclohexanesulfonyl peroxide, tert-amyl hydroperoxide, tert-amyl peroxy-2-ethylhexanoate, tert-amyl peroxy-2-ethylhexyl carbonate, tert-amyl peroxyisopropyl carbonate, tert-amyl peroxydodecanoate, tert-amyl peroxy-3,5,5-trimethylhexanoate, tert-butyl monoperoxymaleate, this statement is merely illustrative and not restrictive. It is also possible to use mixtures of different initiators for the free radical reaction.
[0128] The suitability of an initiator or initiator mixture for a free radical reaction depends on its decomposition kinetics and the required conditions to be met. By fully observing these boundary conditions, a person skilled in the art will be able to select the initiator appropriately.
[0129] In the case of preparations which, in addition to olefinically and acetylenically unsaturated groups, also contain silicon-bonded hydrogen, there is the possibility of curing by hydrosilylation. Suitable catalysts for accelerating the hydrosilylation reaction are the catalysts known from the prior art.
[0130] Examples of such catalysts are compounds or complexes selected from noble metals, including platinum, ruthenium, iridium, rhodium and palladium, preferably metal catalysts selected from the platinum group metals or selected from compounds and complexes of platinum group metals. Examples of such catalysts are metallic and finely divided platinum, which may be present on a support such as silica, alumina or activated carbon, and compounds or complexes of platinum such as platinum halides, for example PtCl 4 , H 2 PtCl 6 x6H 2 O、Na 2 PtCl 4 x4H 2O, platinum-olefin complexes, platinum-alcohol complexes, platinum-alkoxide complexes, platinum-ether complexes, platinum-aldehyde complexes, platinum-ketone complexes, including H 2 PtCl 4 x6H 2 O and cyclohexanone, platinum-vinyl-siloxane complexes such as platinum-1,3-divinyl-1,1,3,3-tetramethyldisiloxane, with or without detectable inorganically bound halogen, bis(γ-methylpyridinium)platinum chloride, tris(ethylenedipyridinium)platinum chloride, dicyclopentadieneplatinum dichloride, dimethylsulfenthiopheneplatinum(II) dichloride, cyclooctadieneplatinum dichloride, norbornadieneplatinum dichloride, γ-methylpyridiniumplatinum dichloride, cyclopentadieneplatinum dichloride, and reaction products of platinum tetrachloride with olefins and primary or secondary amines or primary and secondary amines, such as the reaction products of platinum tetrachloride in solution in 1-octene with secondary butylamine, or ammonium-platinum complexes. Another embodiment of the process of the invention uses a complex of iridium with cyclooctadiene, such as μ-dichlorobis(cyclooctadiene)diiridium(I).
[0131] This description is intended to be illustrative only and not limiting.
[0132] The development of hydrosilylation catalysts is a dynamic field of research which continuously generates new active species, which of course can be used here as well.
[0133] The hydrosilylation catalyst preferably comprises a compound or complex comprising platinum, preferably platinum chloride and platinum complexes, more particularly platinum-olefin complexes, particularly preferably platinum-divinyltetramethyldisiloxane complexes.
[0134] In the process of the invention, the hydrosilylation catalyst is used in an amount of 2 to 250 ppm by weight, preferably in an amount of 3 to 150 ppm, more particularly in an amount of 3 to 50 ppm.
[0135] In a preferred embodiment, the silphenylene polymer of the formula (I) is applied to a metal substrate in a third step.
[0136] The silylene polymers of formula (I) are particularly suitable for use as adhesives and / or adhesion promoters for the production of metal-clad laminates, in particular for electronic applications, in particular for metal-faced laminates, and in particular for radio frequency applications, in particular those operating at frequencies of 1 GHz and above. Particularly preferred is the production of metal-faced electroplatings for the production of circuit boards in electronic devices, in particular for radio frequency applications.
[0137] The metal coating electroplating layer may contain reinforcing materials, but need not do so. This means that they may not contain or may contain, for example, reinforcing fabrics such as fiber fabrics or nonwoven fabrics. If reinforcing materials are included, they are preferably arranged in layers. In this case, the reinforcing layer may be composed of a variety of different fibers.
[0138] These reinforcement layers help control shrinkage characteristics and provide enhanced mechanical strength.
[0139] If a reinforcement layer is used, the fibers forming this layer can be selected from a variety of different possibilities. Non-limiting examples of such fibers are glass fibers, such as, for example, E-glass fibers, S-glass fibers and D-glass fibers, silica fibers, polymer fibers, such as polyetherimide fibers, polysulfone fibers, polyetherketone fibers, polyester fibers, polycarbonate fibers, aramid fibers or liquid crystal fibers. The fibers may have a diameter of 10 nm to 10 μm. The reinforcement layer has a thickness of at most 200 μm, preferably at most 150 μm.
[0140] A preferred form of application is the use of the silphenylene polymers of formula (I) as binders or co-binders together with organic binders for the production of metal-faced laminates containing glass fiber composites for further production of circuit boards. The preferred metal is copper.
[0141] For the use of the silylene polymers of formula (I) according to the invention, they can be used as the sole binder. They can also be used in the form of a blend with organic monomers, oligomers and polymers.
[0142] Organic monomers, oligomers and polymers commonly used for this purpose include polyphenylene ethers, bismaleimides, bismaleimide-triazine copolymers, hydrocarbon resins, aliphatic such as polybutadiene and aromatic such as polystyrene, and mixed systems with aliphatic and aromatic properties, such as styrene-polyolefin copolymers, in principle there is no restriction on the form of the copolymers; epoxy resins, cyanate resins and optionally other resins, the selection being illustrative and non-restrictive.
[0143] Preferred organic monomers, oligomers and polymers are oligomeric and polymeric polyphenylene ethers, monomeric, oligomeric and polymeric bismaleimides, oligomeric and polymeric hydrocarbon resins, and bismaleimide-triazine copolymers. Here, the organic monomers, oligomers and polymers can optionally be used as mixtures with one another.
[0144] In the preparation of silylene polymers of formula (I) in which organic components are also used, the proportion of organic monomers, oligomers and polymers is 10% to 90%, based on 100% of the mixture of silylene polymers of formula (I) and organic monomers, oligomers and polymers, preferably 20% to 90%, more particularly 30% to 80%.
[0145] Furthermore, not only the silphenylene polymers of the formula (I), but also mixtures thereof with organic monomers, oligomers or polymers can be dissolved in other organic monomers which optionally have olefinically or acetylenically unsaturated groups as reactive diluents, for example styrene, α-methylstyrene, p-methylstyrene and vinylstyrene, chlorostyrene and bromostyrene.
[0146] Typical non-reactive solvents can also be used to dissolve the silphenylene polymers of formula (I) and optionally mixtures thereof with organic monomers, oligomers and polymers, for example aliphatic or aromatic solvents such as aliphatic mixtures with a defined boiling range, toluene, xylene, ethylbenzene or mixtures of these aromatic compounds, ketones such as acetone, methyl ethyl ketone, cyclohexanone, carboxylates such as ethyl acetate, methyl acetate, ethyl formate, methyl formate, methyl propionate, ethyl propionate; in particular, effective solubility of mixtures of silphenylene polymers of formula (I) with organic monomers, oligomers and polymers is most likely to be achieved in aromatic solvents such as toluene, xylene, ethylbenzene and mixtures thereof.
[0147] In the case where the silylene polymer of formula (I) is used in combination with an organic oligomer or polymer or a mixture thereof, it is important to use a silylene polymer of formula (I) that is compatible with the selected organic component and does not cause phase separation. In these cases, more phenyl-rich silylene polymers of formula (I) should generally be used because the phenyl groups increase the compatibility with the organic component. In particular, for relatively aromatic-rich organic polymers such as polyphenylene ethers or aromatic hydrocarbon resins, more aromatic-rich silylene polymers of formula (I) should be used, wherein the bridging aromatic group and the aromatic substituent are bonded to the silyl unit at the terminal, both of which contribute to the establishment of compatibility.
[0148] The precise amount of aromatic groups required to establish compatibility of the silphenylene polymers of formula (I) with the defined choice of organic binder must be determined according to the choice of organic binder.
[0149] Just as two or more organic polymers, optionally selected from different polymer classes, can be mixed and used in an adhesive formulation, two or more silylene polymers of formula (I) can also be combined with each other in an adhesive formulation. In other words, according to the present invention, only a single silylene polymer of formula (I) can be used as an adhesive, or two or more silylene polymers of formula (I) can be combined with each other to form an adhesive formulation. According to the present invention, only one silylene polymer of formula (I) is also combined with one or more organic polymers to form an adhesive formulation. Also according to the present invention, two or more silylene polymers of formula (I) are combined with one or more different organic polymers to form an adhesive formulation.
[0150] Determining the compatibility of one or more silphenylene polymers of formula (I) with one or more organic oligomers or polymers can be readily accomplished by mixing a mixture of one or more organic binders with one or more silphenylene polymers of formula (I), advantageously in a solvent in which all the selected components are dissolved, then removing the solvent by conventional techniques, such as by distillation or spray drying, and subjecting the resulting residue to visual evaluation or evaluation by means of microscopy, possibly electron microscopy. A compatible mixture is evident in the absence of any silphenylene polymer domains that are separate from the organic components and identifiable as a separate phase.
[0151] According to the invention, other formulation components are used, such as additives, which optionally may also include silanes, such as defoamers and deaerators, wetting agents and dispersants, flow control agents, compatibilizers, adhesion promoters, curing initiators, catalysts, stabilizers, fillers, including pigments, dyes, inhibitors, flame retardants, crosslinking assistants, etc., and in principle there are no restrictions on the choice of these components. In addition to compatibility tests in the sense of suitable miscibility behavior, compatibility tests in terms of reactivity may also be necessary in order both to prevent premature gelling and to ensure that all components polymerize or copolymerize with each other sufficiently quickly during curing, and also to test sufficient wetting and optionally other properties. This may need to be kept in mind and taken into account when drawing up the formulation.
[0152] Examples of fillers that can be used are ceramic fillers, for example silica, for example precipitated silica or fumed silica, which can be hydrophilic or hydrophobic and is preferably hydrophobic and which can furthermore be functionally and optionally reactively equipped with organic groups on its surface; quartz, which can optionally be surface-treated or surface-functionalized so that it carries reactive functional groups on the surface; aluminum oxide, aluminum hydroxide, calcium carbonate, talc, mica, aluminum oxide, kaolin, magnesium sulfate, carbon black, titanium dioxide, zinc oxide, antimony trioxide, barium titanate, strontium titanate, corundum, wollastonite, zirconium tungstate, hollow ceramic beads, aluminum nitride, silicon carbide, beryllium oxide, magnesium oxide, magnesium hydroxide, solid glass beads, hollow glass beads and boron nitride. The additional fillers used may be core-shell particles of various materials, such as silicone beads with a silicon dioxide surface covering, and elastomeric particles with a polymer covering, in which case the elastomeric particles may also optionally be silicone elastomers, and a typical example of a surface covering on such elastomeric particles is a polymethyl methacrylate shell. The ceramic fillers preferably have a diameter of 0.1 μm to 10 μm. 90The filler is preferably present in an amount of 0.1 to 60 wt %, more preferably 0.5 to 60 wt %, more particularly 1 to 60 wt %, based on the total binder formulation consisting of one or more binders, reactive monomers, additives and fillers as 100 %. This means that the amount of any non-reactive solvent used is not included.
[0153] Among the fillers, special emphasis should be placed on those having thermal conductivity. These are aluminum nitride, boron nitride, silicon carbide, diamond, graphite, beryllium oxide, zinc oxide, zirconium silicate, magnesium oxide, silicon oxide and aluminum oxide.
[0154] In principle, the adhesive formulation can contain a flame retardant additive in an amount of typically 5 to 25% by weight. However, a specific feature of the silphenylene polymers of formula (I) is that they reduce the requirements for flame retardant additives, since the silphenylene polymers of formula (I) themselves already exhibit flame retardant properties. It is known that polyorganosiloxanes and siloxanes exhibit flame retardant properties, which is also encountered by the silphenylene polymers of the present invention, and they can therefore be used as flame retardant additives themselves. Therefore, a particular advantage of the present invention is that in this case, the function of the adhesive can be linked to the function of flame retardancy. Therefore, depending on the amount of silphenylene polymer of formula (I) used, the amount of flame retardant additive can be reduced. For an amount of at least 20% by weight, the amount of flame retardant additive is preferably only 0 to 10% by weight, more preferably 0 to 8% by weight, and more particularly 0 to 5% by weight, based on the total mixture of all adhesives and reactive organic monomers used; in other words, when using silphenylene polymers of formula (I), the use of flame retardant additives can be omitted depending on their selection and use amount.
[0155] Typical examples of flame retardant additives are hydrates of metal Al, Mg, Ca, Fe, Zn, Ba, Cu or Ni and borates of Ba and Zn. Surface treatment can be carried out on the flame retardant additive, in which case they can optionally have reactive groups on the surface. The flame retardant additive can also be a halogenated organic flame retardant additive, for example, such as hexachloromethylenetetrahydrophthalic acid, tetrabromophthalic acid or dibromoneopentyl glycol. The example of other flame retardant additives is melamine cyanurate, phosphorus-containing components, such as phosphinates, diphosphinates, phosphazenes, vinylphosphazenes, phosphonates, phosphaphenanthrene oxides and fine-grained melamine polyphosphates.
[0156] Other examples of bromine-containing flame retardant additives are bispentabromophenylethane, ethyleneditetrabromophthalimide, tetradecabromodiphenoxybenzene, decabromodiphenyl ether or brominated polysilsesquioxanes. Certain flame retardant additives are synergistically enhanced in their effect. For example, this is the case with the combination of halogenated flame retardant additives and antimony trioxide.
[0157] Other examples of additional components are antioxidants, stabilizers against weathering degradation, lubricants, plasticizers, colorants, phosphors or other agents for marking and tracking, and antistatic agents.
[0158] The silphenylene polymers of formula (I) are preferably crosslinked as part of producing the metal facing laminate.
[0159] The crosslinking aid used includes in particular polyunsaturated, free radical curable or hydrosilylated monomers and oligomers, as shown in the following non-limiting examples. They include, for example, diethylenically unsaturated components, such as symmetrically ethylenically unsaturated disubstituted disilanes, such as 1,1,2,2-tetramethyl-1,2-divinyldisilane, 1,1,2,2-tetramethyl-1,2-dipropylmethacryloyl disilane, with, for example, diallyl, divinyl, diacryloyl or dimethacryloyl-substituted diethylenically unsaturated disubstituted organic monomers or oligomers, such as conjugated and non-conjugated dienes, such as 1,9-decadiene, 1,3-butadiene. They also include, for example, triethylenically unsaturated monomers or oligomers such as 1,2,4-trivinylcyclohexane, triallyl cyanurate or triallyl isocyanurate, tri(meth)acrylates, such as trimethylolpropane trimethacrylate.
[0160] Also included herein are monomers and oligomers having unsaturated substituents, such as 2,2-bis[[(2-methyl-1-oxoallyl)oxy]methyl]-1,3-propanediyl dimethacrylate (pentaerythritol tetramethacrylate), tetraallyl cis,cis,cis,cis-1,2,3,4-cyclopentanetetracarboxylic acid, tetraallylsilane, glyoxal bis(diallyl acetal).
[0161] Due to the possibility of hydrosilylation curing in addition to free radical curing, multi-Si-H functional components can also serve as crosslinkers, for example 1,1,2,2-tetramethyl-1,2-disilane, 1,4-bis(dimethylsilyl)benzene or oligo- and polyorganosilanes with multiple in-chain and / or terminal Si-H functionalities.
[0162] Suitable catalysts and initiators for the free radical curing of adhesive formulations consisting of silphenylene polymers of formula (I) and organic monomers, oligomers and polymers are the same as those already identified earlier above (thus, in particular peroxides). In addition, in order to initiate the free radical curing of both the separate silphenylene polymers of formula (I) and the adhesive formulation, there are other suitable free radical initiators, for example azo components such as α,α′-azobis(isobutyronitrile), redox initiators such as peroxides such as a combination of hydrogen peroxide and iron salts, or azides such as acetyl azide.
[0163] The silylene polymers of formula (I) and the preparations containing them can be used as solvent-free or solvent-containing preparations used according to the present invention. Usually, they are used as solvent-containing preparations to promote the uniform distribution of all components of the preparation and to promote the wetting and saturation of any reinforcement layer used. Usually, reinforcement layers are also used. Glass fiber fabrics are preferred. The saturation of the reinforcement layer can be achieved by the impregnation application of the preparation, and there are various available technical solutions for the preparation, including optionally continuous methods, and the selection thereof is not limited in any way for the purpose of producing the metal-faced laminate of the present invention. A non-limiting example of an application technology is impregnation, where appropriate, the web of the reinforcement material is impregnated by a roller system in a continuous operation (spraying, flow coating, blade coating, etc.). The advantage of the present invention is that all available technologies can be used without limitation and modification, and no special new method for using the silylene polymers of formula (I) is required. Therefore, in the production of metal-faced laminates, the present invention is completely in the prior art. The new feature is the use of the silylene polymers of formula (I) for producing the metal-faced laminate, which is hitherto unknown.
[0164] The impregnation is followed by a drying step, in which any solvent used is removed. For the drying operation, the prior art is also used. In particular, these techniques include heat-induced evaporation with or without reduced pressure. By appropriately setting the reactivity and viscosity of the adhesive mixture used, the product of this step is a storable composite material under suitable conditions (e.g. cooling), which can optionally be further processed at a later point in time.
[0165] In the final step of the method, the adhesive preparation is polymerized again according to the prior art. Any initiators for free radical polymerization used here are heated above their decomposition temperature, so that they decompose, form free radicals, and initiate free radical polymerization of the adhesive preparation. In principle, radiation curing techniques can also be used.
[0166] If hydrosilylation curing is used instead of free radical polymerization, the temperature employed in this step is a temperature suitable for deactivating the inhibitor used with the hydrosilylation catalyst employed and for releasing the catalytic activity of the hydrosilylation catalyst.
[0167] This step is usually carried out at an elevated temperature of preferably 100 to 390° C., more preferably 100 to 250° C., more particularly 130 to 200° C., wherein the temperature is effective for a period of preferably 5 to 180 minutes, more preferably 5 to 150 minutes, more particularly 10 to 120 minutes. High pressure is usually used in this step. Conventional pressures are 1 to 10 MPa, more preferably 1 to 5 MPa, more particularly 1 to 3 MPa.
[0168] In this second step, lamination of the composite material with the conductive metal layer is carried out by applying a layer of at least one selected metal to one or both sides of the composite material consisting of the reinforcement layer and the adhesive formulation before curing occurs. In other words, between the first step, which comprises impregnation and drying, and the second step, which comprises chemical curing of the adhesive preparation, the composite material from the first step is laminated with at least one conductive metal.
[0169] Suitable conductive metals include in particular at least one selected from the following: copper, stainless steel, gold, aluminum, silver, zinc, tin, lead and transition metals. In principle, there are no restrictions on the thickness of the conductive layer or its shape, size or surface texture. The conductive metal layer preferably has a thickness of 3 to 300 μm, more preferably 3 to 250 μm, more particularly 3 to 200 μm. In the case of using two layers, the thickness of the two layers of at least one conductive metal can vary and does not need to be the same. Particularly preferably, the conductive metal is copper, and in the case of using two conductive layers of conductive metal, both layers are copper. The conductive metal is preferably used in the form of the metal foil. The average roughness Ra of the metal foil used is preferably at most 2 μm, more preferably at most 1 μm, more particularly at most 0.7 μm. The lower the surface roughness, the better the suitability of the respective foil in radio frequency applications, which is a preferred purpose of the present invention. In order to improve the adhesion between the conductive metal layer and the composite material consisting of the adhesive formulation and the reinforcing layer, various techniques of the prior art can optionally be used, such as the use of an adhesion-promoting layer, electrochemical deposition of the metal layer on the composite material consisting of the adhesive formulation and the reinforcing layer, or vapor deposition. The conductive metal layer can be directly located on the composite material consisting of the adhesive formulation and the reinforcing layer, or can be connected thereto via an adhesion-promoting layer.
[0170] If no reinforcing layer is used, the layer of the adhesive preparation containing the silphenylene polymer of formula (I) is produced by depositing the layer of the adhesive preparation on a carrier, such as a release film or a release sheet, wherein suitable materials for the carrier are in principle any materials from which the dried or cured adhesive preparation can subsequently be separated again, such as polytetrafluoroethylene, polyesters, etc. The separability and film-forming properties of the respective carrier material must be determined individually depending on the adhesive composition. The statements about this method remain equally valid for this non-reinforced variant.
[0171] From the reinforced or unreinforced composite material from the first step and the laminated composite material from the second step, a multilayer system can be produced by alternately stacking multiple layers of the composite material from the first step, for example, one on top of the other with the facing laminate material from the second step, and then curing the not yet cured composite material from the first step in an operation that essentially corresponds to the procedure for producing the metal facing laminate material. In order to produce thicker layers, it is also possible here to stack multiple layers of reinforced or unreinforced composite materials from the first step one on top of the other in direct sequence.
[0172] Besides being used for producing metal facing laminates, the silphenylene polymers of the formula (I) can also be used in corrosion protection formulations, more particularly for corrosion protection at high temperatures.
[0173] In addition, the silylene polymers of formula (I) and preparations containing them can also be used for corrosion protection of reinforced steel in steel reinforced concrete. In this case, when the silylene polymers of formula (I) and preparations containing them are introduced into the concrete mixture before the mixture is formed and cured, and when the silylene polymers of formula (I) or preparations containing them are applied to the concrete surface after the concrete is cured, the corrosion inhibition effect in the steel reinforced concrete is achieved.
[0174] In addition to the purpose of preventing metal corrosion, the silylene polymers of formula (I) can also be used to manipulate other properties of the formulations containing the silylene polymers of the present invention, or other properties of solids or films obtained from the formulations containing the silylene polymers of formula (I), as exemplified below:
[0175] -Control conductivity and resistance
[0176] -Control the flow properties of the preparation
[0177] -Control the gloss of wet or cured films or objects
[0178] -Increase weather resistance
[0179] -Increased chemical resistance
[0180] - Increased color tone stability
[0181] - Reduced tendency to chalking
[0182] - Reduction or increase of static and sliding friction on solids or films obtained from preparations comprising polyorganosiloxanes of formula (I)
[0183] - Stabilizing or destabilizing foam in a formulation comprising said formulation
[0184] - Improved adhesion of preparations comprising polyorganosiloxanes of formula (I) to substrates
[0185] -Control the wetting and dispersion behavior of fillers and pigments,
[0186] - controlling the rheological properties of formulations comprising the silphenylene polymers of the invention,
[0187] - controlling the mechanical properties of solids or films obtainable and comprising silphenylene polymers of formula (I) or formulations comprising them, such as flexibility, scratch resistance, elasticity, ductility, bendability, fracture behavior, resilience behavior, hardness, density, tear resistance, compression set, behavior at different temperatures, coefficient of expansion, wear resistance, and other properties, such as thermal conductivity, flammability, air permeability, resistance to water vapor, hot air, chemicals, weathering and radiation, sterilizability,
[0188] -Control electrical properties such as dielectric loss factor, breakdown resistance, dielectric constant, leakage resistance, arc resistance, surface resistance, specific breakdown resistance,
[0189] - flexibility, scratch resistance, elasticity, ductility, bendability, breaking behavior, resilience behavior, hardness, density, tear resistance, compression set, behavior at different temperatures of solids or films obtainable from preparations comprising silphenylene polymers of formula (I).
[0190] Examples of applications in which the silylene polymers of formula (I) can be used to control the properties specified above are the production of coatings and impregnation systems on substrates such as metals, glass, wood, mineral substrates, synthetic and natural fibers for the production of textiles, carpets, floor coverings or other articles that can be produced from fibers, leather, plastics (such as films and moldings) and the resulting coatings and coverings. In addition, by appropriate selection of the formulation components, the silylene polymers of formula (I) can be used as additives in formulations for the purposes of defoaming, flow promotion, hydrophobization, hydrophilization, filler and pigment dispersion, filler and pigment wetting, substrate wetting, promotion of surface smoothness, reduction of static and sliding friction on the surface of the cured material obtainable from the additive-added formulation. The silylene polymers of formula (I) can be incorporated into the elastomeric composition in liquid form or in cured solid form. In this case, they can be used to enhance or improve other use properties, such as controlling transparency, heat resistance, yellowing tendency or weathering stability.
[0191] All of the above symbols in the above formulae have their definitions in each case independently of one another. In all formulae, the silicon atom is tetravalent. Example
[0192] The following examples are used to further illustrate the present invention. They should be understood as illustrative rather than limiting.
[0193] Unless otherwise stated, all operations were performed at room temperature, 23°C, and atmospheric pressure (1.013 bar).
[0194] Unless stated otherwise, all data describing the properties of the products are valid at room temperature, 23° C., and atmospheric pressure (1.013 bar).
[0195] This equipment is commercially available laboratory equipment and is provided by many equipment manufacturers.
[0196] Ph represents phenyl=C 6 H 5 -
[0197] Me represents methyl=CH 3 -. Accordingly, Me 2 Represents two methyl groups.
[0198] PPE stands for polyphenylene ether.
[0199] HCl stands for hydrogen chloride.
[0200] In this article, each substance is characterized by reporting the data obtained by instrumental analysis. The following measurements were either performed according to publicly available standards or determined according to specially developed methods. In order to ensure that the teaching given is clear, the methods used are as follows.
[0201] In all examples, parts and percentages are by weight unless otherwise indicated.
[0202] Viscosity:
[0203] Unless stated otherwise, the viscosity is determined by rotational viscometry in accordance with DIN EN ISO 3219. Unless stated otherwise, all viscosity data are valid at 25° C. and an atmospheric pressure of 1013 mbar.
[0204] Refractive Index:
[0205] Unless otherwise stated, the refractive index is determined in the visible wavelength range at 589 nm, 25° C. and 1013 mbar atmospheric pressure according to standard DIN 51423.
[0206] Transmittance:
[0207] The transmittance is determined by UV VIS spectroscopy. An example of a suitable instrument is the Analytik Jena Specord200.
[0208] The measurement parameters used are as follows: Range: 190-1100nm
[0209] Step size: 0.2 nm, integration time: 0.04 s, measurement mode: step procedure. A reference measurement (background) is first performed. A quartz plate fixed on a sample holder (quartz plate dimensions: about 6×7 cm HxW, about 2.3 mm thickness) is placed in the sample beam path and measured relative to air.
[0210] The sample measurement is then performed: a quartz plate fixed to the sample holder and carrying the applied sample (applied sample layer thickness about 1 mm) is placed into the sample beam path and measured against air. An internal calculation relative to the background spectrum yields the transmission spectrum of the sample.
[0211] Molecular composition:
[0212] Molecular composition was determined using nuclear magnetic resonance spectroscopy (for terminology see ASTM E 386: High Resolution Nuclear Magnetic Resonance (NMR) Spectroscopy: Terminology and Symbols), measuring 1 H nucleus and 29 Si core.
[0213] 1 Description of H-NMR measurements:
[0214] Solvent: CDCl3, 99.8%d
[0215] Sample concentration: about 50 mg / 1 ml CDCl3 in 5 mm NMR tube
[0216] Measurement without added TMS, spectrum of residual CHCl3 in CDCl3 at 7.24 ppm Reference spectrometer: Bruker Avance I 500 or Bruker Avance HD 500
[0217] Probe: 5mm BBO probe or SMART probe (Bruker)
[0218] Measurement parameters:
[0219] Pulse sequence = zg30
[0220] TD=64k
[0221] NS = 64 or 128 (depending on the probe sensitivity)
[0222] SW=20.6ppm
[0223] AQ=3.17s
[0224] D1=5s
[0225] SFO1=500.13MHz
[0226] O1=6.175ppm
[0227] Processing parameters:
[0228] SI=32k
[0229] WDW=EM
[0230] LB=0.3Hz
[0231] Depending on the type of spectrometer used, individual adjustment of the measurement parameters may be necessary.
[0232] 29 Description of Si-NMR measurements:
[0233] Solvent: 6D6 99.8% d / CCl4 1:1 v / v with 1wt% Cr(acac) 3 Sample concentration as relaxation reagent: about 2 g / 1.5 ml solvent in 10 mm NMR tube
[0234] Spectrometer: Bruker Avance 300
[0235] Probe: 10mm 1H / 13C / 15N / 29Si glass-free QNP probe (Bruker)
[0236] Measurement parameters:
[0237] Pulse sequence = zgig60
[0238] TD=64k
[0239] NS=1024(depends on probe sensitivity)
[0240] SW=200ppm
[0241] AQ=2.75s
[0242] D1=4s
[0243] SFO1=300.13MHz
[0244] O1=-50ppm
[0245] Processing parameters:
[0246] SI=64k
[0247] WDW=EM
[0248] LB=0.3Hz
[0249] Depending on the type of spectrometer used, individual adjustment of the measurement parameters may be necessary.
[0250] Molecular weight distribution:
[0251] The molecular weight distribution is determined as the weight average Mw and the number average Mn using the method of gel permeation chromatography (GPC or size exclusion chromatography (SEC)) with polystyrene standards and a refractive index detector (RI detector). Unless otherwise specified, THF is used as the eluent and DIN 55672-1 is used. The polydispersity is the ratio Mw / Mn.
[0252] Glass transition temperature:
[0253] The glass transition temperature was determined by differential scanning calorimetry (DSC) to DIN 53765, perforated crucible, heating rate 10 K / min.
[0254] Particle size determination:
[0255] The particle size was measured by dynamic light scattering (DLS) and the zeta potential was determined.
[0256] The auxiliary agents and reagents used for determination are as follows:
[0257] 10X10x45 mm polystyrene cuvette, disposable Pasteur pipette, ultrapure water.
[0258] The sample for measurement is homogenized and introduced into the measuring cuvette without air bubbles.
[0259] The measurements were performed after an equilibration time of 300 s at 25 °C with high resolution and automatic measurement time adjustment.
[0260] The reported values are always based on the D(50) values. D(50) is understood to be the volume average particle diameter at which 50% of all measured particles have a volume average diameter smaller than the specified value of D(50).
[0261] Determination of dielectric properties: Df, Dk
[0262] The dielectric properties were determined according to the split-pin resonator method at 10 GHz using a Keysight / Agilent E8361A network analyzer according to IPC TM 650 2.5.5.13.
[0263] Microscopy Procedure:
[0264] The micro / nanostructures were characterized by optical microscopy and transmission electron microscopy, respectively.
[0265] Optical microscopy:
[0266] Sample preparation: 1 drop of sample (neat) on slide; cover with coverslip
[0267] Instrument: LEICADMRXA2 with LEICADFC420 CCD camera (2592x1944 pixels)
[0268] Imaging: transmitted light - interference contrast, various magnification levels
[0269] Transmission Electron Microscopy:
[0270] Sample preparation: one drop of sample on coated TEM grid (dilute 1:20, adapt as needed if necessary); add contrast agent if necessary; dry at room temperature
[0271] Instrument: ZEISS LIBRA120, Sharp Eye CCD camera (1024x1024 pixels)
[0272] Imaging: Excitation voltage 120 kV; TEM bright field; various magnification levels
[0273] Adhesion peel strength test:
[0274] The adhesion of the metal layer laminated to the composite layer with or without reinforcement material was determined according to IPC-TM650 method 2.4.8 "Peel Strength of Metallic Clad Laminates" in "as received" form (ie, without thermal loading or exposure).
[0275] Mass 285±10g / m 2 , 35μm copper foil with a roughness depth Rz≤8μm and an average roughness Ra≤0.4μm was laminated to both sides of the composite layer with a thickness of 100μm, and cured and laminated for 180min at 200℃, 2.0Mpa, and 30mmHg column.
[0276] Flammability test:
[0277] The test was carried out in accordance with the provisions of UL 94-V from Underwriters Laboratories as a vertical fire test. Prior to the test, the specimens were conditioned as follows: stored for 2 days at 23°C and 50% relative humidity and then stored for 7 days at 70°C in a hot air oven. Flame application was performed using a Tirill burner flame. The flame application time was 2×10 s in each case. As soon as the ignited sample went out, the second burning time began. When the sample did not ignite, the second burning was carried out immediately after the first burning. The length of the test section was 5" (127 mm) and the width was 0.5" (12.7 mm). The tested plate had a thickness of 0.4" (10.2 mm). The plate was fixed in a vertical position at a length of 1 / 4" at the upper end. 12" (305 mm) below the test plate, a mesh coated with surgical cotton was placed. The burner was adjusted to produce a blue flame with a length of 3 / 4". The flame is directed at the lower edge of the plastic plate from a distance of 3 / 8" (9.5 mm). After 10 seconds of exposure, the flame is removed. The flame extinction time of the test piece is recorded. Once the flame development stops, the burner flame is placed under the test piece again for 10 seconds. After the flame is removed, the flame extinction time and glow time of the piece are recorded. This test is performed on five different test pieces.
[0278] Synthesis Example 1: Preparation of silylene polymer from chlorosilane by the method of the present invention:
[0279] 48 g of magnesium turnings (2 mol) were added to a 2 liter three-necked flask glass apparatus with a spherical condenser and a dropping funnel. The apparatus was then evacuated to 10 -3 The device was then cooled to room temperature at 23°C.
[0280] 250 ml of dry 1,4-dioxane purged with nitrogen was added to the apparatus. About 50 mg of iodine particles were added and heated to an internal temperature of 60°C. Under a dry nitrogen atmosphere, 118 g (0.5 mol) of 1,4-dibromobenzene was dissolved in 400 ml of dry nitrogen purged 1,4-dioxane and the mixture was transferred to a dropping funnel. The mixture was metered at a uniform rate over 3 hours with heating to compensate for the exothermic temperature rise that occurred so that the internal temperature did not exceed 65°C. The reaction was then stirred at 65°C for 7 hours to complete the reaction to form 1,4-dibromobenzene Grignard reagent. A gray turbid preparation was obtained.
[0281] The reaction mixture was cooled to 2 ° C, and a mixture of 89.8 g of 0.14 mol of vinyldimethylchlorosilane and 0.57 mol of dimethyldichlorosilane was added to the dropping funnel. This step was also carried out under dry nitrogen as an inert gas. The silane mixture was metered in at a uniform rate over 3 hours and cooled again to keep the temperature below 5 ° C. At the end of the metering, it was stirred for another 3 hours at 2 ° C. The reaction mixture was subsequently filtered through a filter plate with a pore size of 1.2 μm. The filtrate was clear and had a low viscosity. 1,4-dioxane was then evaporated at 120 ° C under a reduced pressure of 20 mbar. The product was a slightly reddish yellow solid, which was then dissolved in toluene to form a 50% strength solution for further processing. 200 ml of completely demineralized water was added to the toluene solution under stirring, the agitator was turned off, the preparation was allowed to stand, and the aqueous phase and the organic phase were separated from each other. The aqueous phase was discharged and the washing process was repeated three more times in the same way. The remaining organic phase was admixed with 30 g of sodium sulfate, stirred for 5 minutes and then separated by filtration through a 1.2 μm filter pad.The toluene was subsequently completely distilled off at 120° C. and a reduced pressure of 20 mbar to give an orange solid.
[0282] SEC: Mw = 1050 g / mol, Mn = 713 g / mol, polydispersity PD = 1.47.
[0283] Silanol and alkoxy 1 Not detectable in H-NMR.
[0284] according to 29 Si-NMR, the molar composition of the prepared silicon-containing part is:
[0285] (CH 2 =CH)Me 2 Si(C 6 H 4 )-: 21.8%
[0286] -(C 6 H 4 )(Me 2 )Si(C 6 H 4 )-: 78.2%
[0287] Here, each bridge – (C 6 H 4 Half of a )-group is counted for each Si atom bonded thereto.
[0288] The product is readily soluble in toluene. An 80% toluene solution consisting of 80% of the reaction product in 20% toluene can be easily prepared. The percentages are based on mass. However, in the use examples, a 50% toluene solution is used because the opposite example has a lower solubility and in this way, the purpose is to ensure comparability. The 50% preparation is shown below as 1.1.
[0289] The silphenylene polymer prepared here is not obtainable according to EP 0913420 since it cannot be prepared by hydrosilylation.
[0290] Synthesis Example 2: Preparation of silylene polymer from alkoxysilane by the method of the present invention:
[0291] The procedure corresponds to that described in Synthesis Example 1 with the following differences:
[0292] Instead of 1,4-dioxane, the solvent used was THF. Instead of the mixture of chlorosilanes, 84.6 g of a mixture of 0.14 mol vinyldimethylmethoxysilane (116 g / mol) and 0.57 mol dimethyldimethoxysilane (120 g / mol) were used.
[0293] In the obtained products, 1 No silanol groups were detected by H-NMR. 1 According to H-NMR, the methoxy group was present in an amount of about 0.1 wt%.
[0294] By means of SEC (eluent: toluene), the following molecular weights were determined: Mw = 1134 g / mol, Mn = 803 g / mol, polydispersity PD = 1.41.
[0295] according to 29 Si-NMR, the molar composition of the prepared silicon-containing part is:
[0296] (CH 2 =CH)Me 2 Si(C 6 H 4 )-: 22.1%
[0297] -(C 6 H 4 )(Me 2 )Si(C 6 H 4 )-: 77.9%
[0298] Here, each bridge – (C 6 H 4 Half of a )-group is counted for each Si atom bonded thereto.
[0299] The product is easily soluble in toluene. An 80% toluene solution is easily prepared, which consists of 80% of the reaction product 20% toluene. The percentages are based on mass. However, in the use examples, a 50% toluene solution is used, because the opposite example has a lower solubility, and in this way, the purpose is to ensure comparability. The 50% preparation is shown below as 2.1.
[0300] The silphenylene polymer prepared here is not obtainable according to EP 0913420 since it cannot be prepared by hydrosilylation.
[0301] Synthesis Example 3: Preparation of the silylene polymer of the present invention from alkoxysilane using a polyhalogenated organic raw material:
[0302] The procedure corresponds to that described in Synthesis Example 1 with the following differences:
[0303] Instead of 1,4-dioxane, the solvent used was THF. Instead of the mixture of chlorosilanes, 67.8 g of a mixture of 0.14 mol vinyldimethylmethoxysilane (116 g / mol) and 0.43 mol dimethyldimethoxysilane (120 g / mol) were used. Instead of 1,4-dibromobenzene, 0.25 mol (118 g) of 3,3',5,5'-tetrabromo-1,1'-biphenyl was used.
[0304] In the obtained products, 1 No silanol groups were detected by H-NMR. 1 H-NMR, methoxy groups were present in an amount of <0.1 wt%.
[0305] By means of SEC (eluent: toluene), the following molecular weights were determined: Mw = 1347 g / mol, Mn = 941 g / mol, polydispersity PD = 1.43.
[0306] according to 29 Si-NMR, the molar composition of the silicon-containing part of the preparation is:
[0307] (CH 2 =CH)Me 2 Si(C 12 H 8 )-: 21.3%
[0308] -(C 12 H 8 )(Me 2 )Si(C 12 H 8 )-: 78.7%
[0309] Here, each bridge – (C 12 H 8One quarter of the )-groups are counted for each Si atom bonded thereto.
[0310] The product is readily soluble in toluene. An 80% strength toluene solution consisting of 80% of the reaction product 20% of toluene is easily prepared. The percentages are based on mass. However, in the use examples, a 50% strength toluene solution is used, since the opposite example has a lower solubility and in this way the aim is to ensure comparability. The 50% preparation is indicated below as 3.1. The silphenylene polymer prepared here cannot be obtained according to EP 0913420, since it cannot be prepared by hydrosilylation.
[0311] Synthesis Example 4: A silphenylene-silanylene copolymer was prepared according to the prior art of Example 1 in EP 0913420 as a non-inventive comparative example.
[0312] The 1,4-bis(benzylvinylsilyl)phenylene and 1,4-bis(dimethylsilyl)phenylene starting materials were prepared by Grignard synthesis. The appropriate procedure was the same as described in Synthesis Example 1.
[0313] Here, in the case of 1,4-bis(benzylvinylsilyl)phenylene, in a first step, a di-Grignard reagent in THF is generated from 1,4-dibromobenzene and four times the molar amount of magnesium turnings based on the amount of 1,4-dibromobenzene used, and in a second step, as described in the examples, this reagent is reacted with two times the molar amount of phenylmethylvinylmethoxysilane based on dibromobenzene. This gives the desired 1,4-bis(benzylvinylsilyl)phenylene, the identity of which is given by 1 H and 29 Si-NMR spectroscopy analysis confirmed. The same method was used to prepare 1,4-bis(dimethylsilyl)phenylene, this time using the corresponding amount of dimethylmethoxysilane instead of phenylmethylvinylmethoxysilane. Here again, the acquisition of the required chemical components can be demonstrated by NMR spectroscopy. At this point, the considerable difference of this prior art with respect to the invention explained here is already obvious, since the cost and complexity of the experiment alone for the preparation of Example 1 according to EP 0913420 are already twice as high as the cost and complexity involved in the preparation of the silphenylene polymer of the present invention. The further conduct of the experiment corresponds in all details to the description according to Example 1 in EP 0913420. As a result, a solid reaction product was obtained, which had a weight-average molecular weight of Mw=19 900 g / mol according to SEC. EP 0913420 does not give the numbers for Mn and PD, so a comparison is not possible here. In the present case, the values obtained are as follows: Mn=3042 g / mol and PD=6.54. 1 H-NMR and29 In both Si-NMRs, the expected signals of the structural groups were found, and the product obtained here was therefore undoubtedly chemically identical to the product according to Example 1 in EP 0913420. The product obtained was soluble in xylene and toluene up to a concentration of 50%. Since no higher solubility was obtained compared to the silphenylene polymers of the invention, this material was used in a concentration of 50% in toluene to compare the properties.
[0314] This 50% preparation in toluene is now referred to below as 4.1.
[0315] Synthesis Example 5: According to Example 1 of US 6072016, a prior art silylene-polysiloxane copolymer was prepared as a non-comparative example of the present invention:
[0316] For Example 1, according to US 6072016, an initial polymer is required, which is prepared according to Reference Example 1 from US 6072016 from 1,4-bis(benzylvinylsilyl)phenylene and 1,4-bis(dimethylsilyl)phenylene, the same starting materials as already described in Synthesis Example 4, and additionally vinyltrimethoxysilane. The preparation of 1,4-bis(benzylvinylsilyl)phenylene and 1,4-bis(dimethylsilyl)phenylene has already been described in Synthesis Example 4. In order to obtain the initial polymer according to Example 1 of US 6072016, it is prepared according to the description in Reference Example 1 from US 6072016. The relative amounts of 1,4-bis(benzylvinylsilyl)phenylene and 1,4-bis(dimethylsilyl)phenylene here differ from Synthesis Example 4 and Example 1 according to EP 0913420. Therefore, vinyltrimethoxysilane is terminally dehydrated and silylated to the remaining Si-H of the 1,4-bis(dimethylsilyl)phenylene used in excess. In this case, the chemical properties of the obtained product can also be analyzed by NMR and SEC analysis to ensure that the obtained product is the same as that described in Reference Example 1 of US 6072016. For the product in the experiment reproduced herein, the weight average molecular weight determined by SEC is Mw=9675 g / mol. US 6072016 does not give the number average molecular weight Mn and the polydispersity index PD. In the case of the present invention, they were found to be Mn=6365 g / mol and PD=1.52.
[0317] In order to remain precisely within the prior art of US 6072016, the obtained bistrimethoxysilyl-terminated silphenylene was cured according to the procedure described in Example 1 of US 6072016, which means that methyltris(methylethylketoxime)silane in toluene was used for the curing. For this purpose, a 50% strength toluene solution of the bistrimethoxysilyl-terminated silphenylene according to Reference Example 1 of US 6072016 was prepared as described in Example 1 of US 6072016. This 50% strength toluene solution consisting of toluene and the bistrimethoxysilyl-terminated silphenylene according to Reference Example 1 of US 6072016 is referred to as 5.1 hereinafter.
[0318] Application Example 1: Use of the silylene polymers 1.1, 2.1 and 3.1 of the present invention and the counter-examples 4.1 and 5.1 not of the present invention for preparing copper-surface laminates:
[0319] The silphenylene polymers 1.1, 2.1 and 3.1 of the present invention prepared according to Synthesis Examples 1 to 5 and the silphenylene-silanylene copolymer 4.1 not of the present invention and the alkoxysilyl-terminated silphenylene-silanylene copolymer 5.1 also not of the present invention were used as adhesives to prepare copper-faced laminates with glass fiber reinforced composite layers. The materials used are as follows:
[0320] Copper foil: 35 μm thick copper foil (285 ± 10 g / m 2 ), with a roughness depth of Rz≤8μm and an average roughness depth of Ra≤0.4μm, and a purity of ≥99.8%.
[0321] Glass fiber: E glass fiber 1080E produced by Changzhou Xingao Insulation Materials Co. Ltd., thickness 0.055±0.012mm, 47.5±2.5g / m 2 .
[0322] In order to ensure comparability of the adhesives, all adhesives in this example were used as 50% concentration toluene solutions.
[0323] To initiate curing, the inventive vinyl-functional silphenylene polymers 1.1, 2.1 and 3.1 and the non-inventive silphenylene-silanylene copolymers 4.1 were each mixed with 1% by weight of dicumyl peroxide, based on the amount of silphenylene polymers 1.1, 2.1 and 3.1 or silphenylene-silanylene copolymers 4.1 used, the peroxide being uniformly distributed in the resin matrix by stirring. 5.1 was cured by adding methyltris(methylethylketoxime)silane in an amount as indicated in Example 1 according to US Pat. No. 6,072,016.
[0324] The laminates are produced by subjecting a glass fiber layer measuring 30×30 cm to a bubble-free layer-by-layer impregnation with the corresponding organopolysiloxane (as a toluene solution, if appropriate) by means of an air removal roller. In the process, the glass fiber layer is mounted on a flat, dimensionally stable stainless steel support, to which a layer of copper foil is applied before the first layer of glass fibers is placed. In total, 3 layers of glass fiber fabric are impregnated successively in each case. To remove the solvent, the impregnated fabric is dried to constant weight in a vacuum drying oven at 10 mbar and 60° C., if appropriate. Thereafter, a second layer of copper foil is applied to the impregnated glass fiber layer, and another dimensionally stable stainless steel plate is placed thereon. The laminate is baked in a heatable press with a pressure of 2 MPa at 200° C. and a reduced pressure of 30 mbar for 120 minutes. This produces a copper-faced laminate with a total thickness of 260±20 μm.
[0325] The dielectric properties were determined at 10 GHz using a Keysight / Agilent E8361A network analyzer according to IPC TM 650 2.5.5.13, using the split-pillar resonator method. The values obtained were as follows:
[0326] Test substance <![CDATA[D k ]]> <![CDATA[D f ]]> 1.1 (The present invention) 3.08 0.0019 2.1 (The present invention) 3.10 0.0020 3.1 (The present invention) 3.10 0.0018 4.1 (Not the present invention) 3.37 0.0033 5.1 (Not the present invention) 3.73 0.0045
[0327] D of the copper-faced laminate made of the silphenylene polymer of the present invention and the silphenylene-silanylene copolymer f and D k The D value is higher than that of the silanylene-silanylene copolymer cured with the ketoxime according to US 6072016. f and D kThe values are much lower because the ketoxime silanes used have a significant organopolysiloxane portion and therefore a higher polarity. This is undesirable considering that radio frequency applications require extremely low dielectric loss factors and relative dielectric constants, and the silylene polymers of the present invention show improvements over the prior art in terms of dielectric properties. Non-silylene-silylene polymers of the present invention are more similar to the silylene polymers of the present invention in terms of dielectric properties, but do not match them. Although they are comparable to the silylene polymers of the present invention in terms of the extent to which polar siloxane bonds are avoided, in the non-silylene-silylene copolymers of the present invention, as a result of the selective mode of preparation by hydrosilylation, platinum residues remain in the product and adversely affect the dielectric properties and lead to an increase in the dielectric loss factor. Therefore, although the chemical composition of the silylene-silylene copolymer itself is in principle suitable for achieving the dielectric properties according to the present invention, it can only be used if the platinum residues are successfully removed. This leads to additional costs and complexity, and therefore reduces the profitability of the technology relative to the silylene polymers that are the subject of the present invention. Furthermore, in the fourth synthesis example, it has been pointed out that the starting materials for the hydrosilylation can be obtained only by two upstream Grignard syntheses, thereby increasing the overall cost and complexity relative to the technology of the present invention and making it uneconomical and no longer commercially viable.
[0328] Application Example 2: Use of the silylene polymers 1.1, 2.1 and 3.1 of the present invention and the counter-examples 4.1 and 5.1 not of the present invention for preparing copper-faced laminates via prepregs:
[0329] The inventive silphenylene polymers 1.1, 2.1 and 3.1 prepared according to Synthesis Examples 1 to 5 and the non-inventive silphenylene-silalkylene copolymer 4.1 and the likewise non-inventive alkoxysilyl-terminated silphenylene-silalkylene copolymer 5.1 were used as binders for producing copper-faced laminates with glass-fiber-reinforced composite layers.
[0330] Instead of building the laminate directly without an intermediate prepreg stage as in Use Example 1, this time the prepreg was produced by impregnating the glass fiber layers (in each case as individual layers) on a polytetrafluoroethylene film with the resin formulation and then drying them in a vacuum oven to constant weight. The set of three layers of impregnated glass fiber fabric produced in this way was subsequently deposited one after another onto a copper foil, and the stacking was completed with a copper foil layer. Analogously to Use Example 1, the multilayer structure was pressed and cured between two dimensionally stable stainless steel plates in a vacuum press under the conditions as shown in Example 1.
[0331] The obtained laminate had a thickness of 290±20 μm.
[0332] The dielectric properties measured on the obtained laminates are as follows:
[0333] Test substance <![CDATA[D k ]]> <![CDATA[D f ]]> 1.1 (The present invention) 3.10 0.0020 2.1 (The present invention) 3.09 0.0019 3.1 (The present invention) 3.11 0.0019 4.1 (Not the present invention) 3.40 0.0035 5.1 (Not the present invention) 3.87 0.0048
[0334] D of the copper-faced laminate made of the silphenylene polymer of the present invention and the silphenylene-silanylene copolymer f and D k The D value is higher than that of the silanylene-silanylene copolymer cured with the ketoxime according to US 6072016. f and D k The values are much lower because the ketoxime silanes used have a significant organopolysiloxane portion and therefore a higher polarity. This is undesirable considering that radio frequency applications require extremely low dielectric loss factors and relative dielectric constants, and the silylene polymers of the present invention show improvements over the prior art in terms of dielectric properties. Non-silylene-silylene polymers of the present invention are more similar to the silylene polymers of the present invention in terms of dielectric properties, but do not match them. Although they are comparable to the silylene polymers of the present invention in terms of the extent to which polar siloxane bonds are avoided, in the non-silylene-silylene copolymers of the present invention, as a result of the selective mode of preparation by hydrosilylation, platinum residues remain in the product and adversely affect the dielectric properties and lead to an increase in the dielectric loss factor. Therefore, although the chemical composition of the silylene-silylene copolymer itself is in principle suitable for achieving the dielectric properties according to the present invention, it can only be used if the platinum residues are successfully removed. This leads to additional costs and complexity, and therefore reduces the profitability of the technology relative to the silylene polymers that are the subject of the present invention. Furthermore, in the fourth synthesis example, it has been pointed out that the starting materials for the hydrosilylation can be obtained only by two upstream Grignard syntheses, thereby increasing the overall cost and complexity relative to the technology of the present invention and making it uneconomical and no longer commercially viable.
[0335] Use Example 3: Use of the silylene polymers 1.1, 2.1 and 3.1 of the present invention and the counter-examples 4.1 and 5.1 not of the present invention in a mixture with an organic polymer for preparing a copper-faced laminate:
[0336] The procedure essentially corresponds to that described in Use Example 2, but this time the organic polymer is used as binder in the form of a mixture with the silphenylene polymers 1.1, 2.1 and 3.1 according to the invention and the silphenylene-silalkylene copolymer 4.1 not according to the invention and the alkoxysilyl-terminated silphenylene-silalkylene copolymer 5.1 likewise not according to the invention for the production of copper-faced laminates with glass-fiber-reinforced composite layers.
[0337] The final solvent-free mixture always contained 30% by weight of components 1.1, 2.1, 3.1, 4.1 and 5.1, respectively, mixed in each case with 70% by weight of organic polymers. The organic polymers were triallyl isocyanurate, NORYL SA9000, an α,ω-methacrylate-terminated polyphenylene ether from SABIC, Mn=2500 g / mol, Tg=160° C., and B 3000 from Nippon Soda, Mn=3200, viscosity=210 poise at 45° C., a liquid polybutadiene with more than 85% 1,2-vinyl structures in the polymer chain.
[0338] The polymers are always used in the same proportions. They are dissolved or dispersed in xylene, wherein 30 parts by weight of SA9000, 25 parts by weight of B 3000 and 15 parts by weight of triallyl isocyanurate are dispersed in 100 parts by weight of xylene.
[0339] According to Use Example 2, the resulting formulations were mixed with toluene solutions of components 1.1, 2.1, 3.1, 4.1 and 5.1, respectively, so that in each case, the specified proportions of 30% of 1.1, 2.1, 3.1, 4.1 or 5.1 and 70% of the organic component were present in the resulting solution. These solutions were then used to prepare copper-faced laminates by prepreg as described in Use Example 2.
[0340] The obtained laminate had a thickness of 290±20 μm.
[0341] The dielectric properties measured on the obtained laminates are as follows:
[0342] Test substance <![CDATA[D k ]]> <![CDATA[D f ]]> 1.1 (The present invention) 3.01 0.0019 2.1 (The present invention) 3.00 0.0018 3.1 (The present invention) 3.00 0.0018 4.1 (Not the present invention) 3.39 0.0034 5.1 (Not the present invention) 3.67 0.0041
[0343] The copper-faced laminates obtained using the silphenylene polymers 1.1, 2.1 and 3.1 of the present invention are k and D f The D values are comparable to those obtained with the silanylene-silanylene copolymer 4.1 which is not according to the invention and with the alkoxysilyl-terminated silanylene-silanylene copolymer 5.1 which is also not according to the invention. k and D f Considering that radio frequency applications require extremely low dielectric loss factor and relative dielectric constant, the effect according to the present invention is very obvious.
[0344] Application example 4:
[0345] Fire test according to UL 94V:
[0346] The test was carried out as a vertical fire test in accordance with the provisions of UL 94-V from Underwriters Laboratories. Test specimens consisting of the silphenylene polymers 1.1, 2.1 and 3.1 according to the invention and the silphenylene-silanylene copolymer 4.1 not according to the invention were obtained from toluene solutions into which in each case 2% of dicumyl peroxide were admixed for curing, the percentages being percentages by weight and based on the amount of dissolved product being 100%. Thus, a solution with a total concentration of 50% contained 1% by weight of dicumyl peroxide. The solutions were each poured to a suitable size and then the solvent was evaporated off in stages in a forced-air oven, initially at 80° C. for 4 hours and subsequently at 120° C. for 2 hours, after which the evaporation residue obtained was cured at 200° C. for 2 hours. The procedure for curing the alkoxysilyl-terminated silphenylene-silanylene copolymer 5.1 not according to the invention with the addition of the ketoximosilane was as described above in Example 1 of US Pat. No. 6,072,016. The process for generating the sample sample otherwise corresponds to the process described for samples 1.1, 2.1, 3.1 and 4.1.
[0347] Prior to testing, the obtained specimens were conditioned under the following conditions: storage for 2 days at 23°C and 50% relative humidity, and then storage for 7 days at 70°C in a hot air oven. The flame was applied using a Tirill burner flame. In each case, the burning time was 2×10 seconds. As soon as the ignited sample was extinguished, the second burning time began. In the case where the sample was not ignited, the second combustion occurred immediately after the first combustion. The length of the test piece was 5" (127 mm) and the width was 0.5" (12.7 mm). The tested plate was 0.4" (10.2 mm) thick. The plate was fixed in a vertical position at a length of 1 / 4" at the upper end. 12" (305 mm) below the test plate, a grid coated with surgical cotton was placed. The burner was adjusted to produce a blue flame with a length of 3 / 4". The flame is directed at the lower edge of the plastic plate from a distance of 3 / 8" (9.5 mm). After 10 seconds of exposure, the flame is removed. The flame extinction time of the test piece is recorded. Once the flame formation ceases, the flame of the burner is again placed under the test piece for 10 seconds. After the flame is removed, the flame extinction time and glow time of the piece are recorded. This test is performed on five different test pieces.
[0348] The results obtained are as follows:
[0349]
[0350] *Not the present invention
[0351] Flammability rating V-0 is the highest flammability rating under UL94-V. V-0 is a requirement for the target application of copper-faced laminates for radio frequency applications. Only the silphenylene polymers of the present invention meet this requirement. In summary, both the synthesis examples and the use examples demonstrate that the desired effects of the present invention are achieved, and that the prior art is improved in a desired manner by the present invention.
Claims
1. Silicon phenylene polymer of formula (I) R a R 1 b Si[Y[(SiR 2 c R 3 d ) e ] f ] g YSiR a R 1 b (I), in R may be identical or different and is a hydrogen radical or an olefinically or acetylenically unsaturated, aliphatic or alicyclic hydrocarbon radical, R 2 are independently the same or different groups, wherein R 2 It may be a hydrogen radical or a saturated or olefinically or acetylenically unsaturated, Si-C bonded C1-C2 radical which may be substituted with heteroatoms. 18 Hydrocarbyl, where the same R 2 Two or more oxygen atoms in a radical are always separated from one another by a hydrocarbon unit, and if two heteroatoms are present simultaneously in one R 2 In the group, the oxygen atoms and silicon atoms do not bond to each other to form Si-O units, but are always separated from each other by hydrocarbon units, while the same R 2 Two or more Si atoms in a group may be joined to each other by direct Si-Si bonds, and the Si atoms are always tetravalent, and the remaining valencies of the Si atoms are saturated by further Si-C bonded substituents, which may be olefinically or acetylenically unsaturated, And R 2 It may also include olefinic or acetylenic unsaturated functional groups, which may also contain heteroatoms, wherein R 2 It may also be a hydroxyl group or a monovalent aliphatic, alicyclic or aromatic, Si-C-bonded organic hydrocarbon group bonded to the silicon atom via an oxygen atom, the organic hydrocarbon group being unsubstituted or substituted by heteroatoms and having 1 to 18 carbon atoms, R 1 and R 3 independently of one another may be identical or different groups and are hydrocarbon groups or monovalent aliphatic, alicyclic or aromatic, Si-C-bonded organic hydrocarbon groups which are unsubstituted or substituted by heteroatoms and have 1 to 18 carbon atoms and which may also be unsaturated hydrocarbon groups, wherein R 1 and R 3 can also be a hydroxyl group or a monovalent aliphatic, alicyclic or aromatic, Si-C-bonded organic hydrocarbon group which is bonded to the silicon atom via an oxygen atom, is unsubstituted or substituted by heteroatoms and has 1 to 18 carbon atoms, Y is a chemical bond or a di- to dodecavalent aromatic, alkylaromatic or cycloalkylaromatic radical or a di- to dodecavalent aliphatic or alicyclic radical having 1 to 48 carbon atoms and containing no heteroatoms in the main chain, wherein the radical Y, if not a chemical bond, is always bonded to the silicon atom to which it is bridged via a Si-C bond, a is a number with value 1 or 2, b is a number with a value of 1 or 2, where the sum of a+b = 3, c is a number with value 0, 1 or 2, d is a number with a value of 0, 1, or 2, where the sum of c+d=2. e is a number from 1 to 12, f is a number from 1 to 12, and g is a number ranging from 3 to 250, The condition is In each silylene polymer of formula (I), at least one olefinic or acetylenic unsaturated group R, R 1 , R 2 or R 3 , All silicon-bonded groups R, R 1 , R 2 and R 3 The sum of all organic groups bonded to Si atoms via oxygen atoms must not exceed 10 mol %, and At least 55 mol % of the groups Y, based on 100 mol % of all bridging groups Y, are di- to dodecavalent aromatic, alkylaromatic and cycloalkylaromatic groups.
2. The silylene polymer according to claim 1, wherein R 2 The heteroatom in is selected from oxygen atom and silicon atom.
3. The silphenylene polymer according to any one of the preceding claims, wherein the olefinically or acetylenically unsaturated groups R, R 1 , R 2 or R 3 Selected from alkenyl, acryloxy and methacryloyloxy of acrylic or methacrylic acid, and acrylate or methacrylate of unbranched or branched alcohols having 1 to 15 carbon atoms.
4. The silphenylene polymer of any one of the preceding claims, wherein Y is a bridging aromatic unit having 1 to 24 carbon atoms between 2 to 12 carbosilyl units.
5. The silphenylene polymer according to any one of the preceding claims, wherein the bridging aromatic group Y has the formula (IVa), (IVb) and (IVc) The group R 10 , R 11 , R 12 and R 13 It may be a hydrogen radical or a substituted or unsubstituted hydrocarbon radical or a radical of the formula OR 14 A group in which R 14 is a hydrocarbon group, and adjacent groups in formulae (IVa), (IVb) and (IVc) may be coupled to each other to form a cyclic group, thereby producing a fused ring system.
6. The silylene polymer according to any one of the preceding claims, wherein all silicon-bonded groups R, R 1 , R 2 and R 3 The total of all organic groups bonded to Si atoms via oxygen atoms is not more than 1 mol %, based on the total of 100 mol %.
7. The silylene polymer according to claim 1 , which is liquid in the non-crosslinked state and has a viscosity at 25° C. of 20 to 8 000 000 mPas, determined by rotational viscometry in accordance with DIN EN ISO 3219, or is solid and has a glass transition temperature in the range of 25° C. to 250° C., determined by differential scanning calorimetry (DSC), perforated crucible, heating rate 10 K / min in accordance with DIN 53765.
8. The silphenylene polymer according to any one of the preceding claims, Where g is a number with a value of at least 5.
9. A process for preparing a silphenylene polymer of formula (I) according to any one of the preceding claims: R a R 1 b Si[Y[(SiR 2 c R 3 d ) e ] f ] g YSiR a R 1 b (I), in The compound of formula (VIII) [Hall] o -Y(VIII), in Hal is a Cl, Br or iodine atom, o is a number from 2 to 12, and Y has the meaning indicated therein in claims 1 to 8, reacting with magnesium and a silicon-containing compound selected from the group consisting of compounds of formula (IV), (V) and (VI), R 15 h R 16 i Si(IV), R 15 j R 16 k Si[SiR l 17 R m 18 ] n SiR j 15 R k 16 (V), R 15 j R 16 k Si[SiR l 17 R m 18 ] n -X 1 -[SiR l 17 R m 18 ] n SiR 15 j R 16 k (VI), in R 15 is a halogen atom or a C1-C3 alkoxy group, R 16 , R 17 and R 18 are independently groups R, R 1 , R 2 or R 3 , but not a group of formula (II), and R 18 may additionally be a halogen group or a C1-C3 alkoxy group which does not contain functional groups including carbonyl or carboxyl groups, hydroxyl groups, double-bonded nitrogen atoms, primary, secondary or tertiary amine groups or thiol groups, X 1 is a chemically bonded or divalently bridged aliphatic, cycloalkyl aliphatic, cycloalkyl aromatic or alkyl aromatic hydrocarbon radical which does not contain a functional group comprising a carbonyl or carboxyl group, a hydroxyl group, a double-bonded nitrogen atom, a primary, secondary or tertiary amine group or a thiol group, and is represented by the formula R 19 -X 2 -R 19 Hydrosilylation of a hydrosilylatable olefinically or acetylenically unsaturated precursor Z produces 19 is an olefinically or acetylenically unsaturated hydrosilylatable C2-C8 group, and X 2 is a group X shortened on either side by C2-C8 1 , h is an integer with a value of 1, 2, 3, or 4, i is an integer with a value of 0, 1, 2 or 3 and the sum of h+i=4, j is a number having a value of 0, 1, 2 or 3, wherein j has a value of 1 at at least one terminal Si atom of the disilane, oligosilane or polysilane of formula (V), such that at least one group R is always present per molecule of formula (V) 15 , k is an integer with value 0, 1, 2 or 3, where k+j=3, l and m are each a number with a value of 0, 1 or 2, where l+m=2, n is a number ranging from 0 to 50, and Compound of formula (VIII) [Hall] o -Y(VIII), in Hal is a Cl, Br or iodine atom, o is a number from 2 to 12, and Y has the meaning indicated therein in claims 1 to 7.
10. The method according to claim 9, wherein the compound of formula (VIII) is selected from 1,4-dibromobenzene, 1,4-dichlorobenzene, 1,2-dichloroethane and 1,2-dibromoethane.
11. The process according to claim 9 or 10, wherein the process is carried out in ether.
12. The process according to claims 9 to 11, wherein the process is carried out in stages, first reacting the component of formula (VIII) with magnesium and in a second step adding the desired selected components (IV), (V), (VI) and (VII) respectively.
13. Use of the copolymers according to any one of claims 1 to 8 as binders or as additives in formulations for the production of coating and impregnation systems and the resulting coatings and coverings on substrates.
14. Use of a copolymer according to any one of claims 1 to 8 for the preparation of metal facing laminates.
15. Use according to claim 14, wherein the metal is selected from copper, stainless steel, gold, aluminum, silver, zinc, tin, lead and transition metals.
